POLA PIKIR DALAM NOVEL INDONESIA MODERN - -, suroso (LITERA, 2015)
<img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAWcAAAFLCAIAAACFtNqXAAAgAElEQVR4nOy9Z0AUWdo27M7z7M7u7OQx6xhGUZQgkhGQIJKjApJBcg6Sg+Scc24ykhtoyUlyjgKScw4N3UDT3dB0fT/O9/bLi86MCjM6u1y/iqLq1KnTp+5zh+u+zwnoGMf4f7G1tRUSEiIrK6uhoVFQUHAkbaLRaF9fX0tLS1dX18nJybi4OEtLSzQafSSNH+NPxolP3YFjHOMYfzEcS41jHOMYH4ZjqXGMYxzjw/CrUmNvb49AIPz2zWtrazs7O4fsAQqFwmKxv3EBkUg85COO8V8FLBb7+XhMxsfHR0dHP3Uvjhi/KjXQaPTGxsZv34zD4fb29g7Zg5WVla2trd++Znp6en19/ZAPOsZ/CQgEAh6P/0wWGzQajUKhPnUvjhh/AQuFSCQuLS39rmQ5xjGO8efgryE13ucyPB7/u8rRMY5xjMPjLyA13hM7Ozvb29ufuhfHOMZ/Pv5zpMYxjvFXx+7u7uEdhX8CjqXGMY7xueCv4r87lhrHOMbngvX19b+ElX1YqUFyVR7wWX4mca/PCkQi8XhYjvEbwGKxu7u7n7oX78bCwgKJnHUEUgOLxa6uroI/FxcXy8rK+vr6PuLzWFtba2tr6+/vP2SXPlusrKx8XJRnc3PzL6G4HuM/FUQicXNzc3d3F3zXR2ChWFtbi4uLAy9OWVnZiRMnnj59+s4rNzY24HD4wsLCO//b1dX1/fffy8jIHL5Lnyd2dnZ+l277TqBQqOOg8jE+HxxWaiCRyNOnT584caKtrQ2CoImJiW+//VZcXLy0tLSnpwdcs7Ky0t/fj8fjY2Jivvnmm66uLgiC0Gg0EonE4XBoNHp4eBgc/Pzzz1paWhAETU1Nzc7OHrJv/+U4toaO8QfhsFIjIyNDVFT07Nmz8vLyEAQRCAQKCopz586xsrKePXs2KCiopqaGjY1NWlrax8fH0tLyb3/7m4CAAA8Pz82bN1lYWOBwuLGxMT09vbS09Pz8/J07d4yMjFJSUoSEhIqKio7iBf97gcFgVlZWPnUvjvEfiENJDSKRyM/PLy8vT0ZG9uOPPwLt4Oeff1ZQUNjd3RUVFb169aqRkdFXX32lpqZWXFzs7Ox87ty59vZ2FRWVEydOJCcnv3nzBg6HMzAw/O1vf2tsbBQUFDx79uyNGzcGBweP6AX/e0EkEo/WIb+5ubm5uXmEDR7jL4pDSY36+npqamp7e3sTE5MTJ04EBQWtrq7+4x//ePz4MQRBUlJS7OzsTU1NBgYG169fFxcXj46O/vHHH/F4vLu7+48//ghBUHp6Oh0dnZyc3E8//dTQ0HDv3r0zZ858//33lpaWxwr2ZwUikYjH4z9bD/8x/kx8vNTY3NwUFBTk4eGBIKizs/O7776joaHJy8ujpqa+cuWKnJzckydP+vr63N3dzc3NRUVFZWRk0tPT/+d//kdNTU1EROTLL78cGxuztbX917/+xcrK+uWXXzo4OFy+fFlYWNjOzu7rr7+2trY+utc8xn8Ltra2frvwwjEOj3dIDTwePzs7+7vefiwW29ra2tHRsbu7Ozc319zc3NTUNDExMTEx0dvbW1VVBX684eFhT0/PqKiozc1NDAaTmpqanp6enp4eHR09PT09OzubmJhYXl7+4sWLly9fFhYWlpaWbm5udnV1lZWVHasbnwo4HO4vmt89OztL4gEc45D4tQ/wHVJjd3cXhUL9JfjwnzmIROLhqxZ9Emxubs7Pz3/qXhzjUwKHw/3aHDhmlP+BIBKJc3NzH8fROMYxPi329vZwONw7/3UsNX4fSCRyYWHh45SvnZ2dT2hnodHoxMREEnEGgEgktrW1RUdHfxDflEgkvn79Ojo6enx8/Ki7+TvA4XCNjY1/UDG3+fl5V1fX4uLio212eXn55cuXR55UMjk5mZiY+KGUPwKBcLRu7M9XahQWFoaEhLx8+RKCoNra2q6urt3dXU9PT3t7+0NOoMnJyfj4+N8Yx9LSUgsLC9KfFhYW3Nzcn8pa3tnZ+W2BNTU1VVZW9s5/YbFYcnJyc3PzA+fT0tL+/ve/Ly0tfVBPWlpaTp069WvP+l3gcLjExMSPEDpIJFJLS6u3t/fjnvvbWFtbo6OjMzU1PcI2R0dHe3p6DAwM3vYNFRUVhYaGfmiDCwsL6urq4+Pjc3Nznp6eH2T2bm1tqampTUxMgD8xGAw4OMxi9vlKjZiYmH/9618IBAKCIE5OTl1dXQiC7OzsVFRUwAXv89p4PP7tk69evRIXF4f2+R0ONNXb25uTkwOO0Wh0YWEhHR3d3NwcBEFIJJK0gCCRSJLoQSKRB1YA0DgWiyUQCEDT29nZWVtbA70iEAgrKyudnZ0QBO3u7uLx+M3NzcnJSQiCxsbGmpubgV0zPDxcXFwMlILe3t7Xr19DELSysjIxMdHW1jY0NARBkIODAz09PWBSdHd3d3d3gw4sLS21t7cLCAjY2dkdGIGRkRE5ObmmpqaWlhY8Ht/f39/T07O2tgYe8bZJ1drampWVNTw8zMfH9+LFCzgcjkQiIQiampqKi4sD5JrGxsaenp6cnJylpaWGhobMzEzwzaBQqOTk5JcvXw4PDzMxMVVXV4N+xsfHT0xMTE9PFxUVZWVltba2zs/Px8TE1NTUHHj63NwcAoFYWFjo6OgoKipKS0srLS09cM3e3l5bW1tJSUlmZmZBQQGQsxUVFZGRkQMDA0gkMj4+vqOjY3Z2NiYmZnZ2FofDvXjxoqCggEgkqqur29jYQBBUUlISFRXV3t5+oPGNjY2MjIykpKSlpaXZ2dmcnJzMzMz09HQIghITE11dXcfGxvbPoq2trbq6usLCwvn5+djY2KSkJFtb25ycHCKR+PTpUzIysq6ursnJyefPnwcHB8/NzYWHh0dHRzs4OAwNDdXW1jo5OaWkpOzs7KSlpdnb28fGxlZWVp4+fdrX1xcOh0dHR/f09Hh5efn4+FhbW6ekpEAQtLCw4OLioqenFxYWRpoAAAMDA9988429vf3y8nJ8fLyhoaGjo+OHLhgH8PlKDRQKJSAgEB0dPTk5eebMGRYWFgwGY2NjU11djUQiExMTnZyc4uPjMRgMDAbz9PS0srLy8/OLjY198uRJSUnJ7u5uenq6sbFxZGTk4OCgubm5jo6OrKwsmNZ2dnYjIyOurq66urqVlZX7n0skEr29vQ0MDPb29nJzc3V1ddnY2O7evbu6upqSkqKpqSktLd3c3JyQkKCurs7Dw/PmzZuEhAQDAwN5efmWlpb9TfX397OxsdHS0nJxccXFxfn4+BgbGxsaGgYFBVFQUIiJifHz8+vr6+fm5t6+fZuWlvbp06cREREWFha6urrq6uqJiYlqamra2tqRkZGhoaE6OjqPHj1yc3OTl5e/du2anJwcGRlZdXW1lpbW2bNnY2NjHRwc7Ozs+Pj4goODq6urDQwM7Ozszp496+7ufmBsJyYmaGhoDA0NxcTEbG1tDQ0NGRgY1tbWeHh4goKC9stQAoFga2urqampoqKSkpJy7949UVFROTk5CQmJ5eVlGxsbMzMzBgaG1tZWaWnpGzduiIuLu7m5ubi4yMrKPn36dHl5WUNDw8HB4eHDh15eXpcvXzYzMwPj4OPjw8fHFxMT89NPP927d09TU1NUVDQkJMTNze2A/M3Pz7927RoCgTAxMbl27Zq5ufndu3dLSkr2X4NGo6WkpM6ePWtnZ3f79u2cnJyUlBR1dXUfHx8WFhYEAnHt2rUXL1709vaysLA0Nzc/efIEBoPJycnZ29tbW1tHR0fHxMQ8fvw4JiYmMjLywHC9fPkyNDRUXFzcwsKir6/v/PnzLCwsz58/NzMzMzc3j4qKYmVlBesBCTAYjJWVdXp6moKCgpWV1dnZ+dq1aw0NDdLS0hQUFDAYTFFRMS0tTVBQ0NXVlZub+9KlS9ra2k5OTuLi4mlpaUBD5ODgCA4Ojo+Pz87OPn36dFRUlKOj46VLl4aHh2/cuCEtLZ2WlkZNTd3a2qqlpQWHwx0dHc+dO3dAarS0tPzwww/h4eH+/v5SUlLDw8Nqamqamprv9RH+Cj5fqQFBkJaWlqSkZGBgYFJSEgMDQ1RUlLW1NQqFcnZ21tbWbmxspKCgiIqK0tDQAFSRc+fOWVpa2tnZcXBwZGdnc3FxJSUlXb16NSgo6Oeff7a0tAwKCqKnp9/e3l5YWLCwsGBhYYmKijrwqROJRGdnZ1ZW1urqamFhYSQSmZGRwcbGlp+ff+HChcbGRgUFBRkZmaamJgQCcfLkyZCQEEVFRQ0NjeTk5Kmpqf1NAYLs48ePX716xczM/PTp0/j4+Fu3blVUVNy8ebO0tHRpaenmzZtwOJyWltbLy6umpubnn38ODAx88eIFJSWlrq4uMzOzh4dHdHT0hQsXzMzMJCQkZGVl3dzcmJiYIAiSkZFxcnIKCQnR1NTs7u4+deqUi4uLgoKCoqKitLQ0oOTLycm9zXwZGRlhZmZeW1vr6+ujoqKCw+F3796tra01NDQ8YIq3trbS0dGtra1hsdjBwUE2NraGhob5+fkrV65MTk4WFBS4ubl9+eWX5eXlkZGRoqKiBAKhs7MzOjpaRETk7t27BgYGILFofHz89evXDx8+HB0dpaWlVVFRsbe35+TkHBgYuHPnTmtrKwqFkpCQEBcXDwoKOuBwwePxfHx8JSUlycnJgEAoKSnp5OR04KUcHR1ZWFggCFJQULC3txcSEsrLy4MgiJ2dPTY2NiQkRENDIy4uLi4urrKy8quvvjI3N5eRkQkKCrKysoLBYFVVVczMzPLy8hkZGQdabmlp8fb2FhQUVFJSgiBIUFAwPT19ZWXlypUrOjo64eHh+vr6B6zmyspKZmZmCIL4+PiAhcjCwlJVVRUTExMYGFhXV3fp0qXQ0FBLS8uUlBR9fX0zMzMIgqSlpW/fvh0WFubu7o5AIBQUFB49euTo6NjU1MTJyYnH42tqasA78vLyRkdHQxDExMSUn59vamrq7u5uZWUFTu7HysoKFRUVEom0tLRUU1ODICg0NJSNjQ06BD5rqZGSknL27FkVFRUikWhqanrjxg1PT08Igh4+fJiWlgZBkKGhoYaGRmRkpLq6OgRBfHx8L1++bGxspKOjMzIy4uHhiYqKcnBw6O/vv3v3bnl5ORKJ5OPjA5tl9PT0aGpqsrCwODo6HrBQCgoKwJoJDJnGxsaHDx+Gh4efOnUqJiYmIyOjoqLC3Nzc2dmZkZExOTm5vb3dxMTk1q1bUVFRB15BRUUlMDAQgiBKSkoREZHCwsL+/v7R0VEODo6pqSk8Hs/IyNjQ0PDgwYP6+vrFxcWffvrJz8/v9evXXV1d3d3d4eHh9+/fZ2VlvX79enBwcHNz89LSUlBQEJAaz549c3d3d3d3FxAQ6OzsPHfuXHJy8uzs7PLyMi0tLTCyWFlZgfq9H0NDQ2xsbJubm/X19ezs7Gg0WkND4/Lly/n5+eACLBYLxqS7u/vChQvAklpdXWVmZm5ra5uamqKmps7KyuLg4GhsbPzHP/5BWo0hCLKyslJVVXVzc7t9+7alpSU7OztYh+fn59nZ2Xt6epiYmNTV1efm5qanpxcXF8nJyVtbW9FodElJSVBQ0JUrVzo6Ovb3dnZ2lpycvLy8HAaDCQsLQxAkKirq7Ox84KVsbW3p6OggCJKWlnZ0dJSRkfHz8yMSiTw8PHA4fGlp6dKlS4KCguvr683NzV9//XVWVtbq6urW1paMjIyZmdnAwEBNTY2BgQEjI+OBlsXExExMTIyMjB48eLC9vS0gIIBAILBYLD09vaWl5eLi4uLi4gGzDg6H3759e2dn5969e9ra2hAE3b59u6ioKDU1lZ+f/+XLl2RkZCUlJVNTUxgMRk5OTk9Pj0gkGhoakpOTv3nzZmpqqra2tqioKD09/dKlSxkZGVRUVNXV1bm5ueTk5Jubm7S0tMHBwRAEUVFRlZWV5efnk5OTR0REzMzMHOj88vLyL7/8EhcXFxISwsHB0d7erqOj4+vrCx0Cn7XUmJiYOHHihKOjIwRBra2tJ06cAOvA06dPxcXF5+bmZGRksrKyDAwMuLi4lpaWbty4kZ6enpeXd/fuXR8fH2pq6o6Ojr6+vrGxsR9++AEGg7169erq1avAQwGDweBwuK2tLQ8PD8ndCJwRz549u3z5cnFxMSUlpaenp5iY2Ndff11QUEBPT+/q6opAIJKTk3/55Rd9fX0qKiphYWFra+vy8nJ+fv6goKD9/UcikRQUFA8fPlxaWgoJCWFhYfHw8IiIiBgbG7t586aUlJSTk5O/v//ExAQZGZm3tzeBQFBXVxcVFYXBYElJSc+fP3dzc9PQ0AgMDDQyMhIUFHR2ds7Pz3/69Om5c+fm5+fV1NSUlJTy8/PPnz+fmZmppaUlLS3t7OxcXV0dEBBAT0+vr69PTU2tr69/wPU7NzfHzMz85MkTHR2dxsZGCILi4uJu3rxJWjBRKBT4DIhEIrBB7OzscnJyGBgYgoODJycn+fj4PD09BQQEjIyM6OjoLC0t5eTkeHh4VlZWIiIi7t+/r6ioyMrKWl9fr6ioqKSkZGtrOz09LSoqqqamBofDubi4DA0Nvby8IiIiyMjIYmJixsfHJSUlHR0ddXV1DyTdlZeXX7161dLSUllZmY6Obn5+3sDAwMDAYL+s39rakpeXp6enX1hYsLa2NjIyamhoEBISevbsmampKVCgFBQUSBqKubm5sLCwiYnJy5cvJSUlDQ0Ng4ODlZWVLSwsYmJiDsxDYGFpaGgAG4qfn9/IyIhAIOTl5bGzsysoKERFRe33WBOJRC8vLy4uLh8fHwEBARUVFSQSqa6u7u7u3tLSwsLCUlBQkJCQIC8vb25uXl1d/fjxYxERkdHR0a2tLWNjYxUVFW9v78zMTGlpaWNj45SUlM3NTUNDQxMTk7y8PH19/YiICGDnEggEV1fX9PR0KysrZmZmZWVlGhqaA+7q3d3dsLAwW1vb1dXVyMhIS0vLFy9eHJI++1lLjd3dXV1dXRA4XF9fNzExAW6nwcFBNTU1PT29hISEhYUFIyMjCwuLly9famlpxcXFDQwMGBoaNjU1hYeHS0lJeXh4lJWVKSkpxcbGjoyM6Onpge8kPz9fV1fXxcWlr69v/0OxWCwMBgsICJienq6oqHj27BkMBgsJCenv7x8bG3NycnJxcZmcnCwqKgoLCysuLo6KioqPj/f29gb68H7MzMwEBQX5+fmB3bcyMjI8PT1ra2sXFxcZGBiMjY2BETE4OJibm1tUVLS7u4vFYouKijIyMt68eTM0NBQVFQXcLhgMBg6H5+fnz87OlpeXFxcXLy0t9ff3V1RU7O7uVlZWDgwMQBBUXFxcWloKfMBVVVWNjY1IJLKvr++AV5hAIExPT5eUlJDKEaSmptrb2//aD1FWVlZbW7u+vj48PDw+Pr6zszM/P9/f3z84ODg1NbW5ufnmzZvBwcHBwcH19fW9vb3h4WEUCjUzM7O1tbW3t9fb2zs9PQ1B0MLCAvD4otHonp6elZWVmZmZoaEh0I3JycnXr1+/7cBeX18fHR0dGBgYHBwcGRnZ3NxEo9EzMzP7pQYWix0dHR0bG8PhcBgMBpiKc3Nzb968IV2Dw+FwOBzprtHR0ZGRESwWOz8/v7a2hsFg3rx5A1aUAyASiaSBApVpVldXgVRdX18fGxt72zEPzpCCHQeiYOC/ICBK+hfpgEAggGMikfhOsg/pJGhndXUVeFixWOzt27cTExPfvuVo8VlLjf0/BpFI3D/0e3t7wA8MAhDQ/wmXHPh5fo2m8mnR0NBw6dKl5ubmT92R/x8+Pj68vLwgQPP++DzZa9vb2/9tKXY4HE5eXl5HR8fc3NzU1PRPKI/wDqmxt7eHwWA+zznxn4GMjAxeXt74+PiPu31vb6+xsfGouOpEItHV1fVtRekvisnJyUOGFf+K2N3dbW1tPUDnO0Ic2GzoHVKDQCAsLi6+/6Q8JPfxvyRFjUgkLi8vA90HKEQfSjbdX9gZi8Xu7e0dydB95uMPuvf+Y7W3t/f2xTs7O+9k7gB8JgsksPsORHD39vYmJycPxOYO4O33fecgHAZbW1v7VZgjsFA+eZ4bEHOglu/a2tri4uLw8HB3dzeQjqAy+Pb29mH6ubS0lJqa+j6yfHt7u6+v721v097e3tbW1scpCJmZmRYWFr8x79+J7u7u3t7epKQkIyOjA3PxAAC9an19vbKysqKiAoKgiIiIurq6j+jq+2N1dTUmJubtAeno6AABMgiC9vb2PDw8Hj16dJiyqS0tLfz8/IAu+E4A5sgHEY6RSOTOzk5vb6+RkdFRkYa7urpoaGhSU1P3n0Sj0SIiItLS0r8h3H19fQ/4MjIyMt4m6RwhDiU1srKyIiIiPvp2HA4H8mttbGze6YUCAPVgfiNxG4lE8vDwgFCrtra2jIwMLy8vLS1ta2sruGB2dlZdXX0/Jfnt32BxcbGuru7XJAsKhaKiovLw8Pjdl1pcXBQRESEReH8DoA+ZmZmZmZm/fWVKSsrFixc/NKkhNjY2ISEhNjaWhobmtyWOtbW1paWlk5MTHR0dqPZcXFwsKioKQtR/EPr7+0FxFhLAgHR2diYlJZFOhoeH09PT/25rv7bDBgRBjx8/TkhIwOFwJBrIgWsKCwt/+eUXwHZ9G6S7CAQCuHFxcVFYWHhra2t5eTkgIABItP3tQxAEHNsHHkeaw8DNub8w2t7e3sLCwoMHD8LCwvbfMjMz4+npycfHB84ABzP418rKCqho0dbWBnzhc3Nz4+PjBAKhp6enqakJdGNgYADItY2NDSQSOTk5+dtLyPvgw6TG3t7eysoKaX1oaWn56BVpb29PX1+/vr5+Z2cnISHh134zgJcvX4qIiIDjnZ2dA3Xo1tbWQkNDx8fH6enpg4KCWlpaEhIS+Pj4GhoagIm7vb1dVlaGQqGIROLg4OD+IunAzY7BYCIiIh49ekQgEObn5ycnJ8FKAh6EwWCqqqoEBQWDgoJ6enpKS0vX19e7u7urqqqAxbG6uopAIABbbGJioqKiYmVlpbm5ubGxsaysbHZ29vXr1yC0QSQS8/PzIyIiBgcHwTwQEhJ68ODB5ubm+vp6ZGRkYGDg8vIyqXsLCwuRkZGmpqYUFBRgYoWHhyckJGxtbXV0dERERERGRmKx2JGREX9//7i4uFevXiUmJsbFxcXHx8NgsM7Ozrq6unv37gUGBrq5uYFoUXl5ubu7O9ApIAgaGBjg5uYGypqHh4ecnBw4LyoqmpycDI7z8/MDAwMnJydrampQKFR5eXlAQMDW1lZRUZG9vX1YWNja2lpGRkZwcLClpWVCQkJaWpq+vj4YkPr6eicnp+Tk5L6+PhcXF0dHRx0dndzc3NHRUQUFhYGBAS8vL2traxAvxOFwISEhgGnS0tLi7u4uIyNz9+7djY2N3t5eHx8fFxeXubm5mpoae3t7T0/PtbW1oaEhNzc3Ozs7EifyzZs33t7eTk5OxcXF8/PzFy5cABrB8PDw2tpaSkqKs7NzVFTU7u5uf3+/r6+vnJwcDQ3N3Nycj49PWlra7Oysra1tTU0NBoMJDg6WlpaOjIysrq42MTHR0dGZmJgoKir69ttvvb29AwICTE1NUShUS0vL8+fPVVVVCwoK2traZGVlNTU1BQQECgoKQJdWVlYAHdHR0XFxcdHExOTJkyfy8vJ6eno4HG5sbMzDw0NXV/enn35KSEiAIIhIJC4sLHh4eKirqwMaMR6Pf/HihYWFhYyMDJhO6urq3NzcMBhMRUUlLy+vrq7OyMhIQUGhoKBAT0/P2dkZjUbb2trq6emJiIjU1dU5OjpSUlIKCAgwMDAc0gPyYVKDSCSi0WhgB25ubhoZGeXm5ubk5Dx8+FBPT09ISKitrS0+Pp6FhaW8vHxwcJCXlzc9PX18fPz58+fGxsY9PT0lJSU6OjoaGho1NTVkZGS6urrx8fEgz6evr8/Q0FBGRkZJSamsrCw9PV1TU1NJSWllZcXW1vbrr7/Ozs6uqamxtrbW1NR8Z3hJSEgoNjYWgqC5uTlqamopKakHDx7AYLDi4mIuLq6mpiYbGxtjY2MrKyuwipaXl8vIyJibm4eHh9vZ2V29evX58+esrKzPnz9vbm6+cuVKfX19Z2entbW1i4vLlStXIiIiIiIiLl68uLi4qKGh8fTp052dHRwO5+zs7OHhwcTElJWVFRMTw8LCMjAwwMzMzMDAoKenR05ObmlpycbGFhYWlpOTIy4u7u3tDYPBIAhaXV1lZWWlpqYGxHBvb281NTUKCgoQpxweHn706FF0dDRoZHh4WEhIyMPDg5eXV15enpWV1d3d3c3NLSUl5cmTJ1FRUQYGBgEBAT/88AMDA4O2tjagabe0tJw+fdrT0/Pp06f8/Pz+/v5iYmJJSUlXrlwBCReJiYn8/PxgAP39/WVlZcGxlZUVaYeKgIAAcnLympqaH374oaCgIDw83NzcPDs7m5+fv66uTkBAwNXVVU9P79atW9nZ2RcuXLC0tNTS0uLi4nr16hUvL29YWNjly5ednZ3Jycnl5OTc3NzOnj27vLw8MzOjq6tLR0cXHx8PrJKdnR0VFRVhYeH29nZBQcGGhgYvLy96evrOzk4aGhpAf5CWls7Pz09MTDx//jwMBnN0dHzy5El6ejrQJXE4nLi4eHJycl5e3p07d0pLS2lpaf38/MA67+rqysvLC4PBvvvuu6CgIAkJibq6utDQUGpq6o2Njbt376qrq6+url69etXBwcHGxiYgIKC0tDQoKCgzMzMqKoqGhsbd3b2kpOTChQuZmZnJycnXrl0rLS1lYmKqr6+vrq6+ceMGIGKFhIT4+vqCZiEIWlxcTEhI8Pb2Pnv27NjYmLKysqCgYGdn58WLFxEIhKioaH5+/tzcHCcnJ4koaG5ubmRkhEajvby8ZGRkioqKrl69WlRUxM3NLRCimagAACAASURBVC8vLycnNzY2VldX19LSIiws7OzsbGdnJyYmlpOTMzw8bGtrq6Ki4uHhAbQ5KyurR48ehYWF0dPTLy0tSUlJvU38+yB8vIVCJBLl5eXV1NS6u7v//e9/9/X16erqGhoaAoJjdHT08vIyDw9Pc3MzKytrfHy8s7OzsLDww4cP3d3d09LSysvLb926BWhLp0+fXlhYEBISCg0NTUpKOnnyZF9fX2lpaU5Ozpdffpmbm+vp6UlFRTU8PHz79m1nZ2dvb28GBoYDti4Oh3v48CGQGpubm4C2CIfD79y5s7y8TE1NnZKSQkVFpa6unpOTA3SE0NDQ69evOzo6Njc3BwUFiYuLb29v8/Ly+vr6Li4uXrhwoaysTEpKKiQkBIIgZWVlV1dXLBbLxcWFQCB0dHTA0r27u1tVVeXo6Hj16lVHR8fZ2dnvv/9+eXlZSUnJzs4OjUZfvHhxZmbG2tpaVFQ0JSUFJICA1GwikWhgYGBubj40NHThwgUIgjY2Nr766iuwyL948YKTkxOCoO7ubnZ29ri4uJ9++snV1dXW1jY4OFhbW5uTkzMoKEhVVVVRURGCIAKBMDU1defOneHhYQiCLCwsVFVVq6urOTg4IAhaWlri4+OjoKDg5+cvLCwEKRUQBAUEBABmLThWUFAAxyClBRzPz8/fu3fPwMDg3r17Kioq1tbWwOgDFI+MjAyQZgISC+/duwd4jXR0dFpaWrdv346JibGxsenq6pKUlExPT0cikdevXx8ZGYEgqLi4+NGjR0JCQuHh4eBZcXFx8vLyQUFBAgICEAQ1NTXdv38f2GgeHh7BwcFwODwtLQ0Gg9HS0oaEhPT29kpLS/Pw8IBVemBg4O7du8Dg5eDgyMnJkZOTA4m2RCLx4cOHDAwMmZmZKSkpISEhtLS0EARNTExQU1NDECQpKQkIl48fPw4KCmJgYAC7cEAQFBwcHBAQwMPD4+LiMjs7C64nEomsrKxxcXGXL18Gl925cyc6OpqVlbWtrW18fJySkhK4S5qbmw0NDX18fK5fv45Codzc3J49ewZBEBsbW0xMDBUVFdBqhYWFSRwzcXFxYK0EBAQoKiqmpqaePn06Njb21atXMTEx9+/fJzlxNTQ0XFxc3rx54+HhwcLCAoPBwBJiYGAAfvqEhAQpKSkfH58HDx5AEKSrq2tiYvKx3z0EHdKv4ebmpqWlNT09DZi8ycnJYCzc3NyoqKjMzMwKCwuHhoZOnTrl5+eXkpKSmZmZkJCgoKDAxcVVWVkpLCzc29uLw+GoqKhWV1ft7e2VlJTCwsIKCgowGIyBgYG7u/uVK1eSkpKKiooEBQUhCPr2229NTEwKCwsPJI9AELS7u/vgwQMQzpycnOTk5FxeXm5sbLx16xaBQGBlZS0oKEAgEFpaWtTU1CBNc2xsDAaDgfwCb29voJyLiIgAM+HChQvT09Ps7Oz+/v4QBLGxsQEJ7eLicvHiRVdXV/Dc1dVVRkbGlJQUQUFBa2vr1dXVH3/8EY1Gq6ure3l5YbHYGzduLC0tWVpacnBwtLW1FRcXKykp3bt3D9xuaGioqqra0dHxv//7v4ODg0tLS1euXAHmQ2pq6uXLl4EG/vPPP4O0l5SUlJmZmeHh4fz8/Pb2dkpKSkpKSmZm5r6+PjQaPTk5eenSJUBtEhISUlNTq62tJScnHxgYSExMNDIy0tDQePjwYV9fX39/P7A0IyMjwdhCEGRtbf3w4UMwgx0cHKSkpMB5wMtmZGScm5s7deoUSGdwc3NjYWEZGxszNzd3cnJycHAQFhbG4/GUlJR5eXkZGRm//PKLv7//jRs3SkpKRkdHkUgkIyNjSEjI5OTkxYsXgZKclJRUUVHx/PlzAQEB8Bk4ODjw8vJmZ2dfv369qKhIU1Pz22+/RSAQZGRkISEhQ0NDlZWV5OTksbGxFBQUJiYmVVVVTU1NampqXFxcEAStra3R0tIGBga2tbUJCgoCAw0k2kIQZGlpeefOnbq6uvb29srKyvPnz+fm5qqrq585c2Z9fV1FRUVUVDQ3NxekiklJScnLy1dXV7e0tFy4cCE4OJidnf3JkydTU1MXLlxAIBBVVVVnzpxBIBDABnz16pWoqGh6evrXX3+dm5tbWlp68uRJQPBzdXW9ePFiQkLC6dOnKysrQYIJDoejpKSMiori5+fX09MLDw//+9//7uDgALrq7e19+/bt0NBQRkbGO3fu1NbW3r1719fXNykp6dWrV/fv39fU1ExLS+vr62NkZJSRkXFxccnNzdXU1AwNDVVUVGRmZs7OzqahoQkODlZVVc3IyACU4s3NzWfPnomKin6oc30/Pl5qYLFYZWXlhw8flpeXf//993Nzc87OzhISEjgcbmNj45tvvgGCfH19nYmJydvbu6+vr7W1NSAg4PXr10Dx5uDg0NDQqKur++GHH6qrqxEIBFBuW1tby8vLz5w5ExYWdu7cOW1tbQQCce7cuaKiosePH0tLSyckJNTU1ISGhpIWKAiCmpubv/nmGxsbGxwOV15efvbs2ZqamqysrB9++CE3N/fSpUuurq4mJiZZWVnCwsJgX8jg4GAzMzN/f38bG5uKiorLly8DGigTE5OysvLp06eLi4tDQ0NpaGhUVVUvXbokISFBJBKHhobOnj0LCKYQBK2srNy8eVNWVpaenp6fnz8yMvLMmTOenp4cHBxCQkIhISEUFBS5ubkwGIybm1tFRUVbW9vIyIiUWJmYmEhOTp6YmOjp6SktLa2npxcdHQ2+n42NDV1dXU5OTgUFBUZGxsbGRm9vb15eXm1tbTgcrqSkBOjSnZ2dWlparKysDg4OcDhcTEwsICBgcXFRWlpaSUmppKREQkKCl5fX3t5+ZWVlZWVFT09PVFTU09MTuFcbGxs5OTl3d3eHh4dVVVWlpKRANoqGhoaPjw9peLOzs4Ee5+vrCzxt6+vrZmZmhoaGYWFhq6urZmZmWlpaBQUFsrKy/v7+o6Oj8vLy7e3tYWFhKioq4eHh1dXVYmJikZGRKysrKioqpExzHR2d58+fA3MJj8ebmJjIy8sPDw97eXlJSkp6eno+evSoubn51atXioqK9vb2NTU1Tk5O2traLi4uVlZWsbGxBgYGDg4OJFu9oaFBS0vLzs6ut7e3rq7uwYMHpNEGqY/S0tK+vr4rKyuJiYmPHz+2t7c3MDDo6OiYnp4GpPLAwMC8vLyZmRlgI3d2doaEhGhrawcEBISHh6NQKA8PDxcXl8zMTCsrK7DNqKmpqaOj4+joaGtrq4WFRXV19djYmL29PVif5ubmHB0dg4ODY2JiUlNTfXx8oqKitra2EhMTKyoqgOQNDg4ODQ2Njo4G0pxAIMTExHh7ezc2Nubl5a2srLx+/frZs2fe3t6Li4vz8/OOjo4BAQF9fX1wOLyioqKystLf3x+BQKytreXn52dnZwMCbnx8fG1tLQRB5eXlWVlZGxsb09PTZWVln0ZqAAePvb09DAZzcnLq6Ojo7e2NjY0Ffs3MzMxXr16BKxsbG1VUVLS0tGprax0dHTU0NBISEvb29uBwuImJCRwOt7CwSE9Pd3BwAGkU169fNzc3DwsLCwwMTEhICAwMXFpacnZ2zsnJWV9fd3V1NTMza2trQyAQ+8Np9fX1UVFRqampSCSyra0tJCSkpaVldnY2ISEhPj4+Jiamvr4+KysrMjISKPAQBI2NjYWFheXl5YHQSU5OTk9PD5FIzMvLq66ufvPmDaBLdnd3NzY2Tk9PA3/b1NSUqqrqfgLiyMhIU1PTzMxMT0/P4OBgS0tLV1dXe3t7V1cXEonc2tqanZ0lEokYDGZ9fb21tRXUxQDeUCKROD4+DqxuJBL5dhhvbW0Nj8cDNjQEQevr6ysrK4CJt7CwQOrG+vo6CoXa3t4mEAhoNBqPx+Px+O3tbTA51tbW9rMSkEgkadLs7e0pKCgkJyeDW4Dzv729nZGR8W2awNuhCpJnGuxsjMFg9vb2SOEDMLDgX0QicXd3FxwQiUQcDgf+C/pMahbsawnOkM6DAxIPmNQBENfAYDAHIri7u7vgzM7ODjjeHzfZzxgmPeLXGKXvHyw/KgrCZ86ggT4Jo/ydPw8ej6ehoSkpKSEQCPfu3bOysvrzO/Y+KC4uFhAQyMrK+tQdOUp0dnaqqqruj0y5uroCf+0xjvE2Ppc8lJ2dHaCGWFhYeHt7H3nBxaNCamqqv7//x60Gn+caAnq1X/uAIGh/9PfAle9z8pCdOcZH4M8cus9FagAgkcj/4K1JPzmJ9qMBrIBfY15vb2+/s27gB2FpaemdyaMfh+Xl5bGxMUCQAWeAfTQ8PLw/C/YAfoMqdniAMWxqagJh9T+i/fb29vz8fDwev7i4uJ+UdOT4Y6UGMNqHhoZAjVOSJX/kv8rExMTLly8PUMVaW1tXVlZ6e3s7OjowGMzAwMBv8/n/IExOTiopKR1ys+v3LIiQlZX1a5OSVGb2Q4FGo1VUVJ49e/bOXw1Eu8TFxd+/ZIO3tzcIcJKwtbX1+PFjUigHgiA8Hj8/P//RkigkJISXl/eAk4hAIEhJSZHogvsBvEUQBHl4eIBA+x+BtbU1JiamP47rHRgYeP36dSQS6efnFxYWRiQSi4qK3ib4Hv7r+8N1DV9f3x9//JEU+mppaTEwMDjyXOacnJxz587trwHV3t6urKwcEBBAQ0NDSUmppKQEh8O1tLT+/O38MBgMPT09qOj1cUhOTn67dNUBgCEVFhYmBXf2n4+Pj99fdf3XcGBwSHais7Mz6WM7UJ4vMzNTWVkZPOUAq3o/9vs7EQgEqeonKfsjPDz83r17JD9lbm6usLAwaHZ9ff1AxQOSW5TkNN3fcwwG09LSws3NfSD5FYlEuri4AHY2yP0jfT/Ozs6gmlZ5eXlDQwM4SWJeb29vA2LxO0dsP29oY2MDdBX4fdfW1kh37e3tra6uKioqgoKMOzs7PT09BAIB+GuRSCSphAdAS0sLaQEYHx+vq6tDoVA4HG52dnZhYWF7extU8SEQCN3d3WDmNzc3s7Gxzc7O1tfXT05Orqys3Lhxo7i4GEQqUChUV1fX+Pj4p5QaBAJhYWFhenq6p6dnY2NjZWWFFPqanZ0FtWcgCJqZmbl79y6oJbGxsbG4uAhmDB6Px2Kx+1cDsIHjO581Ozvb2dkJHOxTU1Pj4+NdXV2kxXNwcDA/P5+WlratrQ2cIRKJIECbmZnZ2NjY3t5+9erVjo4OdXV1UmbU9vZ2Xl5eRUXF1tbW9PQ00B6Liop2dnaam5tzcnImJyfxeHx1dXVNTU1mZmZ3d3dtbW12djaYi62trcHBwR0dHaOjo4WFhbGxsc7OziA4AoDFYmNiYiwtLcfHx52dnTU1NT08PKqqqohEYmNjo6+vb3R09ObmJgKBCA4O9vT0bGhoKCkpcXJyAvlLGxsbISEhsrKy+fn5kpKSjIyM/f397e3tLi4ugBvu5+fn4uJiZGRUXV3t4+NjZGRUV1fn5+cHqvVBEDQ0NOTi4vLs2bOamhoNDY3z58+HhITY2dmpqqoCSq6Tk9P8/LyZmVlSUhIej4fBYLa2tvr6+j4+PkNDQ35+fnJycvr6+jk5OUFBQfLy8hgMJj4+3tzc3MPDA3ztBAJBS0uLgoKiurq6ubnZyspKSkoK8OVVVVWVlZWFhYWBkzU3N1dGRkZMTOzx48cmJiZxcXEbGxteXl4KCgoiIiIwGAzwL7S1tUVFRefm5lxdXU+fPp2SkhIbG6unp6eurg6ID2Dk1dXVhYWF6+rqamtreXl5DQwM7t+/DzhRlZWV1tbW3NzcdHR0JJG0ubnp4+Ojq6tLSUkpISGxsLDAzc2dm5tbUlIiIiLS398vJiZ2/vz5yMhIOTk5OBy+uLhobW2tr6+vq6tbU1Njamqqrq5+oFAbBEHFxcVmZmYqKir37t1LSEjIzs52dnZWUlLKyspSUVHh5eXV1NTk5uaenJycmZkxNDQ0MDC4efOmr6/v9PS0nZ3ds2fP5OTkgoODqaiouLm5SbsroFAoc3NzCwsLUVHR3t7e/Px8QGanpaUtKCigpaUNCgqqqqq6detWV1dXQ0ODtbU1KytrSkpKd3c3FxfX8PCwgIBAenp6Tk7Ov//9b1VV1cePHz948GBlZQW89Yd85e/Gx0uNjY0NSUlJdnZ2JSUlNjY2NTU1cnJyUHHX2NjY2tqamZm5o6MDi8VKS0uDjaBTUlJ8fX1VVVX7+/tFREQePXqkpKRkZGS0u7v74sULOzs7GRkZWVnZtyt9Gxsbg/p3HR0dFBQUEhISHBwcz549293djY+P9/T0VFRUPH/+PKmuzOjo6P3790lbb5SUlLCwsGxtbXl5eUlLS4OTGAyGg4ODnZ19cnKSjIysv79fT09PW1s7ODjYwsIiLCyMnZ29oqKCk5OTjY3Nysrq4sWLz549u3//vqmpKQKBkJCQiIyMpKam9vLyOnHihLGxsaKiIicnJ1hsd3Z2jIyMjIyMnj17FhAQYGxszM7O7ubmdv369fr6+rS0NG9v70uXLhUXF3t5eX3xxRd8fHwpKSnx8fFWVlYnTpyoqqqytLS0srIKDg42NzcXERGRkJAAvNKYmBhQuFhYWPjs2bORkZESEhJiYmK5ubmNjY2gECZ4QSUlJRERkdzc3Pr6enl5eW5u7vLychEREWpqapAzwszMDGr86ujovHjxQlhYeHR09Msvv/T39zcwMNDV1e3q6vrqq69KS0vDw8NVVVVDQ0NFRESqq6tPnjz54sULCIJ2d3ctLS25uLhA/dGmpqY3b96cPHmyoKCAh4dHQkIiKSkJ9GdkZOTLL780NzcvKCh4+vSpqakpyBVCo9H//Oc/o6OjMzIy6Onpe3t7OTk5AwIC3N3d6enpGxoa2NjY/Pz8kpOTSfmNIM/owYMHLCwsc3NzP/30ExwOT0hIuHv3bltb28OHD8fHx3t6enh4eEg+XQ8PD8BbdXR0BFQ0bm7u6OjosbGxS5cu9fX1KSoqCgkJvXnzRlBQMDo62tXVlYGBobCwkJqamouLC9SpPaDEYbFYdnb29PT04uLic+fOJSUlUVFRvXjxQk5OTldXF1CZcDjcnTt3kpKSTE1NQR1gDQ2NgICA58+fc3NzA4pQUlLSjRs3MjIySNM1Li7u/PnzoaGhQkJCSkpKd+7c2dzcnJiYuHbt2uLiopqaWmJiIoFAYGNjq6+vn52dhcFgdHR0T58+7ejoYGdnx+Pxfn5+3t7eMzMzrKysq6uro6Oj3NzcdXV1BgYGH22o7sehGOUWFhbq6upLS0sXLlxoamry9PTk5eWdmZkJDw/39fX94osvAOOYj48P1LDHYrFZWVk3b97c3NxkYWFxcXHp7u6+efNmRUXFrVu32tvbjY2NeXl5DySnTU1NgUrw169f39raApzZxsZGKiqqrKwsdnb2nZ2d2dlZFhYWUpIrAoFgZ2cHx6urq7q6uoDo4ufnR0FBQWo5OTmZj48vMTHxypUrFhYWXl5efX19HBwcwAchICDg5ORkbGwM3gIk0cbHxzMwMCgqKjIyMmZlZenp6ZWVlZ0/fx7sic3CwgLM48HBwV9++QVsk0kgEAwNDYGJwcTElJ2dnZGR4eLicu3ataSkpNraWkZGRgwGg0Qi/f39HRwcvvvuu+DgYG5ubpLqZGBgEBYWVl5e/uOPP8bHx/v4+JSUlOjp6QGCcE1NjYyMDFht9o9bRUWFoqIiDQ1NSkqKl5cX2FDGwcHBwMAAgqDy8nJApnR2dtbV1W1qauLi4nJxcQEFtSMjIwUEBMLCwry9vSEIio6Ofvr0qZqaGgsLC0ifA3xwCIICAwN1dXXRaPSZM2eAdsnAwJCdna2trQ14XAA7OzvU1NSggKOlpaW5uXlXVxc9Pb2/vz8Y3pycHEBg19XVDQ0NTUhIkJSUhCAIDDItLS1pe7TIyEhbW1tJScnbt29DEERHRzc9PT0xMcHHxxcbG3v//n3o/6SlkkwMsIMBBEH+/v4SEhJgTmZmZoL6qRgMxtbWFiz1T58+TU1NVVNTu3LlCgKBqKysrKurA7XOQFbO0tISMIv29vZsbW25uLieP39eUVHR1NT073//Ozw8vKqqan5+XlNTEzyIl5cXvAv4dUBego6ODqjM3tXV1dvbS01Nvd8l5+Licvbs2YKCgv7+fhgM9vXXX29ubo6OjlJQUKBQKCkpqcTERCQSycHBgUKhlJWVPT09dXR0xMXF29ramJiY8Hi8t7e3h4cHDodjYmICY66goEBPTw/GcHx8HLAcPxqH8msYGxvr6OhAEERJSbm8vJyfn6+np+fn5ycsLFxTU3P69GnwU3FwcJw/fx7Mv9bWVsAZFRISSktL29jYAJaFgYGBlJRUcHAwWB8WFhbm5uaAAebg4KChoRESEnL27FlwIxwOHxsbu3fvXmxsLCCMDw0NkZOTk7IG4HA4qOKNx+P19fUDAwPn5uZ2d3cDAwP3p12vrKxcu3ZNVFS0sbHxm2++ef78OR6Pp6OjA2wRUVHRhIQEXV3d58+fQxDEwsLS0NAQHh5OR0dnYGBAQ0PT09MzNTU1MjLyt7/9rbOzE2wCAL6csbGx8+fPu7u7Ly8vo9FoVVVVW1vb7e3tW7duGRsbU1NTp6enU1JSGhoaJiUl0dLSbm9vA80lLy/viy++AGOor6/f19e3vLysp6f36NGjrKysq1evwuHwkZGR5eVlISGhW7duYbHYwMDA/Px8ZWVlVVVV0qvt7e2Fh4eXlZWJiopqaWmlpqbS0dG1tLTIyMjw8fHh8fiWlpabN28mJyeTk5PLyMjs7e2RkZEpKSmVl5ejUKihoaFbt25ZWlrW1NQA3icbG5uHh8e9e/eamppKSkrALMdisQ8ePLh16xYKhbp//76ZmVlJSQk/P39NTQ0lJaWZmRnJM9LW1vbFF1/AYDAcDkdDQ8PDw4NEIpmZmVlZWcPCwiYmJiwtLS9cuAAsfzU1tdTU1AsXLri7u1taWtbX13NwcJD4I3x8fOrq6oqKimfOnCktLf3+++/Lysra29uvXLlSWFhIT0+vqqqqoaFx5swZksmckpJy48YNGxsbGhqamzdvrq2tSUhIAAX522+/ffPmjYODAxkZWU1NDRMTE9ik4saNGy9evMjMzPT29g4PD7e1tdXS0srJyZGUlCSFqGEw2MmTJ83NzZOTk0dGRoSEhGRlZcPDwysrK8XExAQEBHA4HBcXl7+/f2pqKiUlpb29/Y0bN+Tl5fPz85mZmZ8/f56VlQV2zCgqKiKF2Pr7+2lpaU1MTCIiIpqampSVlXl5edXV1X/++WcMBmNvb8/AwKCjo0NBQVFVVSUpKSklJSUgICApKRkQEMDExFRRUaGqqmpiYrKxsUFFRQV2lsjOziYjIwNugcPUkQP4eKmBwWCYmZkZGRlLSkpOnTqVlZWVmprKwcEhLy9PQ0NjY2Nz+vRpeXn5uro6Kiqq2NhYLi4uVVXVkJCQq1evVlVV3b17187Obm5ujoaGBnCEKSgodHV1c3JyUCgUIyMjqSbd48eP7969a2xs/N133/n6+l69ejUwMHBwcBBUu5eQkBAWFlZSUjp16hQcDge3DA8PMzMzDw8Ph4aGnj59mpOT8+bNm01NTSEhIaB+BAkyMjIBAQEQBPHx8QGXBxwOZ2dnB4TlqakpDg4OMTGxrKwsPj6+5OTkwsJCMTExOBwuKysLuNtANy4oKBgaGuLj46uqqgItZ2dnCwgIGBsbg4tVVFQmJiZkZWVdXFyUlZXBvkQ6Ojqmpqbs7OxVVVUDAwOioqKWlpbPnj2Li4tramoSERERExNrbGxsaWnh4eHJzs7Ozs4WFxc3MzOrqKiwsbHR1taem5tLSkpSVFR0c3M74BWCwWBPnz4NDg5eXFycnJzU0dHx9va2sLDQ0dEBrpng4GB9ff2QkJDQ0NCSkpK7d++CGiUKCgqhoaEcHBzm5ubk5OTS0tI5OTkhISFgpzU9PT3glYAgCI1Gh4eHBwQEADXYzc3NyclpaGhofn7ez88vMTEReBaIRCKJ77y5uRkZGRkREZGUlMTJyRkaGqqkpHTjxo3k5OSAgIDJycm6urrw8PD5+fnIyEjA6w0LC0MgEKQAXE9Pj4+PT25ubnx8fHR0dEBAQGNj48zMDEhW6O/vd3d3z83NDQkJaW1tJXn+UlNTfX19CwsLAwICZmZmpqenQeZxWFhYZ2fn2NiYn58f2FohKioKi8UWFxd7enrm5OS0tbV5enrGxMSg0WgJCQlSnsjW1paioqKxsXFYWBglJaW+vv7i4iIQMUNDQ2VlZeXl5Zubm7W1tYWFhRAE5efnp6SktLa2FhcX4/H49vZ2Hx+f2trapqam3Nzcmpqa/dsATk1NZWRklJeXY7FYHA5XWFiYlpZ2584dEBApLS3t6uoaHR3t7++fm5srKSmZm5sDQeXh4eHR0dHBwUFQaKO/vx9orJmZmcAfX1xczMfH90Fb/L6NQ0mN0tJSBAJRV1eXl5fX1taGQqFevnw5Pj6OQCBqa2uHhoaKiooaGxtTUlKamprW19ejoqKKioqKiooqKysLCgpevXq1sbFRWVlZUlIiKSlpbm7+/PlzMjIyZWVlOTk5EpN3dnY2Ozu7tbX11atX4Mvp6ura3t6uqqqanZ3d3NzMzs7u7Oycn5/fr+bx8vIGBQUtLS0BdWB8fHxtbY2fn/9AraTNzU2wdGxsbJDWkMXFRZB2vbu7OzMzMzMzMzc3h0KhQAFu4NInEAiDg4OgXjbA3t4eGo3e71HHYDBLS0sYDAYUGQM1qbFYLBD54KFoNBqFQoFfkRQIIOnAJB2bNBoH+G9gkv2asfprZDmwrIFy3uCMvLy8sbExBEGJiYlsbGxMTExxcXEQBGlpaYEtSI4cGhoaIDsOBoORcvk+Z6DR6PT0dNKIDQ8Pg6zo9fV1UILgD316SUnJd999R1qTPggefoqp8AAAIABJREFUHh7CwsIgkQKFQh2mMBrAZ8Hyqq2tvXLlSm9v79DQEDc3d3Bw8GE4KuBDevXqlby8/P4YTUZGho6Ozkcn7UxMTLxnSgKRSDykLP9zsH8ClZWVCQoKGhoaampqdnZ2ghReAwMDTU3N96lL9rtYXl4+UK6toaFBWFhYQ0PD3NwclKL6axFD8Xh8eHi4pqamtbV1ZGQkCoU64I87kkeQgq8FBQU2NjZAbfkg4HC4gIAA0v5YR4LPQmpsbm46OTnp6+ubmJiUl5cfVbM1NTUkuiGRSOzr6zvMZvTvn8VEIBB+LYT8OWN7e3tpaYmk72xubi4tLR0Vs+btFDIIgnZ2dpaXlz+i6vLa2tpnsn0B2AAcgqCVlRWw1csRAvBZj7bNI8Efzg19/4uB6v62LnAkNdA/lCxM2sbm7ZP/8Tjw1keoAhxVUfVD1o4+xiHxh+saIyMjKSkpv1FM+ADADgAHTK+RkRHgjfsDOvh/UVFRkZ+fD3bKI2XTLy4ugr3I5eXlY2NjNzc3g4KCgC76mVTEP8Yx/mT84VKjsbHx0qVL7+/F2d3dNTQ0JDGOAdra2k6ePPkRRt0HAYFAxMXFNTQ0fPvttyRtE9AE5+bmWFhYXF1d19fX7ezssFisl5fX2xuCHi+Ax/hvwKGkxtzcXHJycmVlJZFIBLtvZGZmwuFw4ALA4/ENDQ0ghE6qiN3f319TUwNCA/39/VVVVYAWtbe3V19fD/YWr6ioAGSNuro6UH0IgiBGRkbg0enp6amrqwObs2MwGFBXdm9vb2JiIjo6Ojs7e3BwsKysDIFAhIWFAZrp1NQUiNItLS2Njo7Gx8cnJyeDDbh3dnZCQkJsbGxaW1sLCwsLCgrW1tZ4eHgAFae1tbW5uRkU2peRkQH0qsDAwNXV1Vu3bgkKCkZERGhpaVVWVpaVlenr65PofUcCsPPDETZ4jGMcCQ6Vh2Jvb29qakpOTt7S0mJjY/Ovf/3L2tr69OnTQUFBk5OT8vLyoDT5yZMnwQYIsbGxoqKipqamMBissLBQUVHRysoKVDYPDAx0dHR88OBBRkYGDQ1Nfn5+aWmpqakpDw+PhoYGBEFMTEwvX76EICgmJuabb75hZWX18fFRU1MLCAjg5+c3NjZ+/Pixh4eHnZ1dZGTk+fPnubm5bW1tf/nll6KiIsC9UVFRERISSk1NPXnypL29vZiYGCjTKiUlFRcXh0AglJSUHj58CEEQHR2doaGhra0tCwuLs7PzzZs3d3d3ZWVlg4KCMjIyvv76687OTjo6Oh0dnYKCgps3b758+TI+Pl5ZWfkwVdXeBtgX6ggbPMYxjgSHkhqFhYVxcXGnT58ODw+vr68HdMzHjx9ra2sHBgaSkZGBK9nZ2cFuFx4eHpcvXwalELm4uAC/lYeHB3A0IAiampoaHh5+8OBBaWnpwMBAWloaSKCAIIiFhQVIDRQKdfv27Tdv3iAQiEuXLuXl5WlraxsaGhobG/Px8bm5uU1OTt67d6++vh6CIHA74IOi0ejbt2+/evWKmZkZpK5JSEgUFRXx8PBISkqWlJQkJSVJSEjs7OwICgoCiicVFVVqaioLCwtoKjIycnp6+p///Of29jaoow1BkIGBAdge4f19N+8DUl7mEbZ5jGMcCT5eaoyNjZGTk6enp5ORkSUkJFRWVl69ehWCoEePHmlpafn6+n7//fczMzPz8/OMjIw1NTUQBPX09OTl5cnJyUlKSt65cwfU71dXVycnJ2dnZwdh0a2tLS4urvz8fHV1dRsbG1dXVxoaGgiC6OjowJ40CwsLv/zyy8LCQlNT09mzZ0tLS0dHR4eGhhAIRG5u7qlTpyIiIri5uYuLi5eXl8XExNzc3M6fP9/f3//69ev79+/X1dVduXJlYmIiLS2Nk5MzNze3qKjo2bNnAgICLi4unJycKBTq559/LiwshMPhenp6xcXFly5dmpmZ4ePjc3BwePXq1YkTJxYXFyUkJJiZmUH9ji+++AJQpCYnJ8PDw49q3+ZjHOPzxMdLjcXFRQEBATU1NR4eHkNDQwcHh5s3b05PT9vb2wsICLS2tsrKyt65c0dFReWnn35ycnKCIMjGxsbc3NzQ0DA8PDw6OpqBgcHZ2dnMzKyrq4ufn5+Li8vW1raiouLUqVMaGhpPnjwRFxfX0NCgp6dPSUlhYmIC5VLS0tKuXr2anJyMwWBkZWVBgeL09HRdXV0XFxcDA4Pe3l4eHh5WVlYrK6uMjIy9vT0bG5snT54YGxuXlJSUlpZycHDU1ta2traqqqpqamqqq6ubmZnl5+c7ODjIyMh0d3draGioqqo6Ozuvr6+/ePGCn58/NDRUVVVVT0/P39+fj4+vvr4ebH4DMh3Y2dkrKyshCGpra9PS0jpaO+UYx/jccChv6MrKyuDg4NbW1uDgYH9///T09NraGgaDGRkZwWAwRCKxubn5zZs3YJ0nEomzs7MVFRWkRPj29vbS0lJArV9fX6+urm5ra1teXm5ubu7p6VleXu7u7l5YWJidne3u7h4fH5+eniYSiZOTk+Pj4yMjI0CHHxwcBJUX5ufne3p6AOWGg4MjOTl5f/HL4eFhwLwC9O2trS1QJhuNRo+MjACPLA6H297eBlVVSGQnDAYDCOBgX3IcDkfaoByYDzU1NUpKSvslxbFZ8bsAFXEAQ/9T9+UYH4zPght6tOju7j537hxIt/2jAYfDKSgoSJV+jvGeABJ/YWHhr8V5WVlZ+fNrwX2G+ARSY3t7+/9j772jokqz9WHX7Z7pudPt2KNtQLERFVEByRKFEhAk55yhyDkWORRFkaHIUSRLzklyjkUUpUByzhmJVef3x7turfqwx2tr90zP/eb5wwV4zqm3Ttjnffd+9vN82gv6KzE5OVlaWgr6BX+/TwFYX1//l2iR/vHx6QnXGe3YP8Ls7HPGQMq4/00O+Gng8fjPL70TCATQS/m7DgngXxA1Dg4OvqYf5Guws7Pzu370mzdvZmdnP/77/Px8R0cHsYH1N8Ha2lpBQcE/LWYlJiYCNarPR09Pj5WV1RkJrH+E7Oxsb29v4Cb1z8Tp6amrq6uvr+9v9US9evVKVlb2a6416Kj29fVVUVH5nI44PB6/u7u7sLAgKCjo5+f3i9u0tLQgEIh/46jxmSgoKHB2dvbw8HBzc/Pw8PD09NTS0voazV4Igtzd3UVFRYm/hoeHAxfCX8TW1tavakLLysoCClGkf8ThcKOjo8BBkig19pkYHx8nynl9jLm5OQoKClK9rN8PeXl58vLyRKreZ2J4eJiCguIzJbmTkpLu3r37iz4sn4OVlZWIiIgvaDUGZtRENeyvBzB//cUy/Ocsx05OTqytrd+/f9/U1HTv3r0zWge/WJ7r6ekB0juGhoZ6enqkqSI8Hg92weFwSUlJpJrPv+Y7ncUfN2q4uLgEBgY6OjqeO3cOFEdVVVVlZWW/5phJSUnADRygo6MDWJYSCARSHxbwc2hoKLgYEAQtLy//4h05OTkJFIY3NjaA7CX0/70kenp6KBSKQCA8ffq0rKxsaGgIXNTj4+Pu7m4Qlc7M1d+8edPW1ra9vR0UFCQsLLy8vPz+/fu1tbWlpaV3796B22h0dLSyspKenj4tLW1kZGRgYGBtbW10dLS/v5/YWkogEN69e1deXj4wMLC9vb22traxsVFSUgLUVcEi7vDwsLu7u7GxEUQELBZLlFMmHZWEhISent7Jycni4iLQUtnY2GhoaKioqHjx4gUOh6uoqMjOzj49Pd3d3QWG7zMzM6enp8AtGY/H5+TkJCQkABYMKQYGBlAoVFxcXG9vLxcXFxqNjo6OBh6OBQUFvr6+w8PDGxsb2dnZKSkpsbGxoCMJg8GARS4Wi3V0dExOTi4sLLx+/XpqaurW1lZFRUVoaOj09DTQdomIiOjo6Kirq0OhUGeaEk5OToSFhQ0NDff392dnZzEYjK+vL1DH6+7uRqPRkZGRQPZxc3MzJycnPz9/e3s7NTXVz88PyEQWFRX5+PiAxNby8nJKSoq1tfXNmzfPyKOfnJwUFxe7ubn5+vouLCwkJiaGhIQAxekz2iiDg4MUFBQ2NjY9PT2AqSgnJwcawevr652cnLy9vc9MMCMjI69cuVJdXe3i4sLCwuLs7IxAIPB4/NjYmK+vr6OjY0VFRXJyclhYWGdnp66urpKSkqKi4tcYlf1xowaoSuTl5XFxcUEQhMfjAwICuLm5ra2tHR0dgVaou7u7qakpUfgPYGtry9/f387OLj4+PiMjw9raemJiwtTUNDMzs76+/u7du46OjhoaGhUVFU5OTikpKZOTkx4eHqamppGRkVNTUy4uLsrKygYGBoaGhsAvGoFAIBAIY2Nj0ukiHo8HApNycnJoNLqhoeHChQtqamqkJj0rKysMDAyMjIwZGRnc3NwiIiLPnj2zt7efnZ01MTHx8fGRkpI685YDTHYnJ6fIyEhVVVVKSsrQ0FAGBoagoCBQcu7q6iosLNTU1DQyMjp//nxJSUlcXBwTE9P8/DxguJBWcwoLC//yl7/U1dWB6e7o6Cg1NfWrV6/QaLSzs7OEhISrq6uAgMCFCxdgMFhYWJienp6tra2AgABQPAX48OEDKysrNzd3dna2rq5uTEzMgwcPoqKiHj58yMHBoaamRklJaW5u/vDhw6ysrLq6Ojc3t+fPn0tLSwMuXENDg6Ojo729vbGxMSMjI+nbsrq6WlJSMiIiQkBAIDk5+dGjR46Ojry8vI6Ojv39/QgEQkVFhZGRcWJigo6O7qeffrK2tn716hUSiaSlpfXw8GhpaVFQUIiMjFRRUfH29r506ZKDgwOQSgMy5Ugk8vz58+Li4mZmZkAJPTY2ljQaHh0dsbOzP3/+vLa2Vk5OLj4+3s7Ojp2dPTExUV5ePiUlBVhkU1BQLC8vq6mpASHCx48fJyUlAXNyfn7+qKioq1evRkVFGRsbFxcXBwUFXbt27cykKT4+XlhYuKOjQ1RU1MrKSkJC4sGDB3l5eXfu3AHy/UR0dHTcunXLysqqr6+PmZk5OTnZyclJQECgqqqKnp4+Ozubjo7OysqKdJewsLB79+719PTY29vDYLCenh4ODo74+HgFBQV3d3cgo+fi4sLNzb2+vn737l0TE5PS0tIzZhG/Cn/cqAGQnp4ORHEhCPLx8eHg4MjJyQEMMRkZGRQKZWpqysrKSnoK8vLyaGhowsPDa2pqwsLCyMjIDg8POTg4DA0Na2trb9++3dTUBJS1tbW11dTU1NTUFBUVQ0JCbty4wcXFFRERMTExERkZCWSs+vr6rl69ikQiY2JiSF8LExMTP/zwAxaLnZiYuHLlSlJSEvCpJd3m+Pj4+fPntra2GxsbzMzMaWlpWCz2/v37vr6+58+fDwwMfPjwIVHPHkBVVZWFhcXDw2N0dBSNRktJSe3t7bGwsERGRk5MTNy6dSszM5OVlRVUr3l4eHJzc/f39x89epSfn49AIMBbiPhgnJ6eSktLR0VFycnJ3bx5Mz093cfHB4vFXr9+3dvbW0dHx8HBwcnJSUNDAyhui4iIxMTEkLb8QhCEx+OVlZV9fHxCQ0Nv3bqVlpamqalZVlZmbGwcHR09OjrKzMy8u7trY2Ojqqo6NjaWmJiopqZGRUV1fHxsamoaHBxMRUVlYmKSkJCgrKxMGtRkZGScnZ0hCNrZ2ens7OTk5Dw+Pn758uXDhw/n5uZiYmIQCAQFBcXR0ZGlpSUCgYAgqLW1FYPBsLKyWlhYaGlpATFaCILa29thMNjy8rKAgICKisqrV69MTExaW1uZmJi2trZGR0clJCSkpaXDw8PPPC3GxsYpKSmlpaVAhhqPxzMwMPzpT38CDCMIggYHB8H89OXLl7q6um/evAHq2SkpKaKiooDiGBISYmRkBDjE6+vrdHR0Z2SlJCQkgA1KQkICFxeXs7MzEHnV0NDIy8sj3XJvb4+fn//t27crKytsbGwEAmFxcZGNjQ2BQJCTk0dHRzs5OZWXl5PGvoqKiufPn0MQ5OTkBG4nfX19Y2Pj+/fvw+HwtLS0ioqK3NxcGAwGQRAIQL/0qP0K/NGjRnJyMlEeztPTE+hEq6qqWllZUVFRmZube3t7YzAY0hXj6uqqoaEhPz+/tbV1SkoK2F1VVTU8PLyurg7MXLq6uvj4+ICzLA8Pj6GhYWFhYX5+/uPHj4la2J6enrq6uhAEJSQkKCoqPn78GIfDET/l7du3586dAwLQDAwMSUlJnJycpK9oANDzBkHQkydP+vv7x8bG6OnpPT09z58/X1NT09PTA+zmidt3dHQA5XRNTU00Gg18GIAs+/DwMB0dHeC2AhttOjq6qKgoCIJsbGwoKCjAz2fg6en5zTffpKenq6urX758ub29HYfDXb16NSkpaXR0dGVlBYFAAMloRkZGRUXFsbGxxcVFUq9DCIKUlZUxGExSUtK1a9fa2tqmp6e3t7eFhYWjo6PfvHnDxsa2vb1tZGSkoqJiaGioqKjo7u4OpHGlpKQQCAQjI6OxsfHU1NTk5CTpqtva2hr4dOzt7WGxWAYGhr29vejo6MePHwPt/9jYWDIyso2NDQ0NDRA1nj9/bmZmJisrq62t7eDg8OTJk+Xl5fX19c7OTlpa2oaGBhkZGTk5uZGRkdnZ2dbW1lu3bi0uLoI1VEREBDk5OWnGYXFxUUJCAoPB9PX1kZGRtbS0DA4OCggIiIiIcHFxTU9Pz87Ogpd/b2+vhoaGgoJCa2trSUlJcHAwGxuburo6IyNjX1/f7OxsXV3dtWvXWlpaAgICzp07dyavgUAgAAfSwcEBuKsICgoCLeKkpCSwDQhnu7u7zMzMSCSysrLy3LlzIyMjpaWl5OTkiYmJ9+/fr6+vx+FwCwsLpFenqqqKmpq6ublZRkZGSEhoZ2eHg4PD1NRUVVUVDoe3tLSMjo4GBgbeuHGjtbX15s2bKBTqKwvef+iocXp6amxs/O23366treHxeFNTU6CvLSwsbGVlxcXFZWNjA7ThSfcqKytLTk5OS0tjYmIqLi5mYmICXhVIJLKuro6CgiI3N9fe3j4zM9PHxwfM6sXFxYuKisrKynR0dB4/fpydnd3c3AzmApGRkfb29mVlZezs7KRLod3dXVlZWX19/ejoaA0NjezsbDIyso911iwsLBgZGQMDA8nIyIKCgtra2v7yl7+Eh4dzc3Obm5ujUKgzg1dSUgoMDDQ3N3dzc0tPT79582Z5ebmPjw8zM7OMjMz58+ejo6MxGAwNDY2ent61a9dAXOvo6Lh06dIvSvXV19dTU1OvrKxUVlby8vKCV729vT0vL6+Tk1NBQQELCwsPD8/q6mpZWRlo20tMTCR9Ic/Pzz969EhQUHBiYkJNTU1aWtrJyamtrU1GRgZ8/adPn3Z1dQHPFA8PD15eXkNDw+fPnxcVFcFgsMDAwNTUVAEBAR0dndzcXNKoMTMzIyUlZWBgEBoaCl4PQABdWloaiUQKCQnZ2toKCgp6e3tLSUnB4fDNzU00Gi0mJgaHw2VlZTs7O+Xk5HR1dcPDw5eWlqSkpCwsLPr6+pSVlc3NzYuKikJCQpiZmauqqiorK7W1tVEoVGZmJmkts7q6mouLS19ff3d3F41GAyuT0tLS9fV1TU1NJSUl4Cpib28vKSlpaGiopaUVExOjq6vr7OxcUFAwPz9vaGgoJCTk4OCwtbXl6+vLx8dna2uro6MD2jWJWF1dBcEiJCRkaWnJ1dXV2tp6aWnJx8eHKBc+PT0NTntERAQ4J5qamq2traOjoyYmJt3d3fn5+fr6+p6enmdaq7e3txEIBKgERUVFLS0tAQuliYkJW1tbYK9VUFDg7+8fHx8fEBCQnJz8lfTlP3TUWFtbs7S0lJaWLisr297etrCwUFNTGx8fB0ZHlZWVmpqaBgYGr1+/Jt2rqalJWVnZ1NS0v7//6OjI1dVVQ0MDiEfjcDh/f39DQ0PQCKerq6uurn50dBQREeHu7l5XV7ezsxMQEODm5tbZ2bmysuLp6VlaWhoeHh4UFITFYs8Mb3d39+XLl1FRUfv7+6Ojo9nZ2e3t7Wei+Pj4eFxcXEVFRV5eXldX19bWVnFxMfArSExMzM/PP9PVisViU1JSqqqqCATC6elpZWXl27dvgWEneMmDqW9nZ2dnZ+fS0hK4gTo7Ow0MDH6xtk8gENbX18HRSIv5OBzuzZs3m5ub79+/Hx8fBzSExcXFgYGBM1XD/f39iYmJ4eFhPB4PZK/n5uYODw83NjZmZ2cXFxfX1tZ2dnZOT083NzePjo6ABPTu7u76+vr6+jr40MXFxZGRkZOTk49FAGdnZ9fW1ra2tsC/QM/54OAACDgfHBzMzMysra2trq4eHR3h8XjwdYiDnJ2dBfVaonkisDU8OTnZ2dkhDmB5efnjXCwejwefC07d8vIyqdDswsICcb0Jkq/AkHF5eZk0bbGwsEBM1hArx4B8TLwE4AdiipSoJg3OANgAWLSRDo/IVP6j4Q8dNUjxmxOBjo6OeHh4fj+r3n8aYmNj2dnZv9J9+j/41wJwtEAfBvGPoJb0LxzVP8K/TdT4AnzavL6yslJDQ+NMhezfDgQCISIiAvT1/REYlv/BFwOPx/+7dOX8X44an8AfSuf6t8J/osbnAHi7/7s8n/8rVldXe3t7SclExNtgf3+/q6uLNIX/W+G3iRrb29urq6uHh4e/6437OQcHvvMfr5+/AMBmPTc3t6Sk5AsIwgQCoampKSEhgbTpZn9/Py4uDmRVPhNDQ0NwOJzoFH8G/f39RF/C/xVnprvgFH3l8wMmdCcnJ19zHLBveXk5MJ3+XeHs7MzLy/tlHCegjY7FYl1dXT9hswzaqcEGJSUl3t7eXz7c/w3t7e23b98mLaYSCIStra3x8fHl5WU2NjZxcfHf/EN/m6hRW1sLZLW+5iB7e3ufWMUFBwd/rO5LiqWlJdAy7+rqCpQ+vxJ+fn4qKirm5uZ/+tOfPuGm29bWBkyAPkZycvLNmzdJqyTAR1ZZWflzBlBdXZ2fn7+4uHj+/Pnc3FzwxzPRMDU19TM9OyMjIz+mhIeFhX29Ac3k5KSJickX9wrW1tY6OTlBEPT69eusrKzP3/HLXgylpaV37twhTQx/5nEmJyeZmZlXVlZGR0eTk5OJecpf3D0lJUVDQwOCoO7u7pycHPDHT8xxNjY2QLL2zNHW19eJRkoQBJ2enpKuqQ8PD3t7e1lZWQsKCkj3CgsLk5CQgCDI1dXVyMhofn6eGOP6+vrOsCK/AF8bNfb29lZXVwkEAj8/f2FhIWlFYH19/R/1BZCeGpB/npiYUFBQIKagz7wK8Hh8Q0MDEDoHning7OPx+KmpKfCzk5MTcEtvamrq7++HIOjg4ACYKkIQBEwVp6enzxz56OgIGDJOTk6enJysra01NTXt7e0tLi7S0dGtr69PTU3913/9FyhVtLW19fT0gB27u7vb2tpWV1efPHliZGQEpDry8/PBR0MQhMVi4+PjWVlZiX8BcHNz09DQyM/Pr6qq2t3d7evrm5mZWVpaio+PJxq1g68mLi7OxsY2NTUlJCTk4uKSlJQE2Otzc3PZ2dnl5eVbW1uZmZldXV1TU1OvXr3KyMgg1XY/OTnp7u4OCQkJCwubnJzk4OCwtLQcGxvLzc21tLRsbm7e3d2lo6PT1dVdW1vr6ury8fHJyspaXl6Oj4/39va2t7evr68PDAy0s7NbX18/ODjIyclxdnZubm7GYrEuLi7Ozs7W1tazs7OVlZXff/99eno6FotFIpGmpqZgnGeueHd3NwqFcnV1XVxcxOPxKSkpsrKyCQkJpqamV65cSU9Pd3FxASbJQNXR0tJyZmYmNTXVysoKjUbb29svLCwMDw9bWVmpqam1tbV9/LjicDhHR0c1NbXW1tbW1lYVFRUzMzM5OTnQAVRTU2NnZ8fHx3fz5k3S22Bzc9PDw8PZ2VlVVdXJySkxMVFMTAwIzTU1NcHhcEVFxfr6+sLCwnPnziEQCB8fHy8vLywWKyIi4uXlNTMzIyEhUV5enpycbGhoaGpqurKyAuRy8/PznZycfH19T09PU1NTlZWVFRUVq6urIyMjJSUlLS0tVVRUlpeXX79+DYfDxcXFidwNgOrqajU1NWFh4ZiYmO7ubj4+PlFRUWlpaUtLS1Bfs7e3NzAwuHTp0pkyoq6uLjk5eXx8PBKJvH37toyMjJiY2NLSUlJSEgKBUFJSAuKVX4yvihoNDQ3GxsYwGKysrMzQ0FBJSUlWVjYwMJBAIMTExFhYWKirq2dkZExNTVlbW9vY2Ghra7e2tqLRaFNT09bWVgiC4uLizMzMDA0Nw8LC/va3vwUFBQ0MDPj7+1tYWEREROTk5ADipp6enp6eXmJiYnNzMyhBKykpvX37NiAgwMzMzMrKamxsjJub+86dO/7+/vLy8kVFRXNzcyYmJra2turq6l1dXbq6usLCwhoaGsrKyqRls83NTRkZGUpKysePH/v5+bm5udnZ2cnJyVVUVFy4cMHNza29vV1YWHhubg6JRJqbmwsLC0dFRSUlJZmYmCgqKoaGhrKysnJychYXF+vr63t5eTEwMOTm5oaHhyMQCDgcTk5OTsoxhyAIg8FQU1MjEIgHDx44Ozvfu3fP1tZ2ZGSEnp6etFft5OSEn5+fkZGxqqpKSEhITU3NwsKCk5Ozo6NDTk4OuLG6u7vz8/Pb2tp2dnZevXpVQEAgJiaGeISxsbG7d+9iMBgUClVeXk5PTy8jI1NaWurr62tvb09JSTk4OEhPTy8vL5+fn8/JyZmTk/PgwQMvLy9GRkZtbW1HR0cKCgoMBsPLy+vv7x8ZGamjowOUnDEYzE8//RQeHi4iImJiYpKfn3/t2rXMzEwZGRkTE5Pw8HBibCXi9PQ0Nzc3LS2NhoYGGEo7OjoWFxdHR0fb2Ng8ePAgOzsbeERWV1cLCgq+f/9eX19fTk4OELRKOXEZAAAgAElEQVRLS0u5uLj8/f319fXFxMQSExOBLuwZ1NbWJicn8/HxaWpq9vf3k5OTR0ZGAhvK+vr658+fT05ORkRE3Lp1i/R9dnx8LCYmxsPDAy66j49PYGAgHx9fR0cHBwfH0NAQoCNHRkaysLBkZmYmJSVRUlKur69LS0urq6tvbW1JSUm9f/++sLAwKyvrwoUL+fn53t7eDAwMs7Oz7u7uMBispKTk+fPnGxsbsbGxvLy8aDT6/v3709PTKioq7u7u1tbWgMJ7pj+4qakpOztbUlKSm5t7bm6OgYEhICBgdHT0/v37NTU1/Pz8Q0NDu7u7vLy8Z6b5Pj4+CgoKHz58iI2NVVBQWF9fZ2Bg8PHxoaKiCgkJkZWVFRYW/vzH/GN8edR49+4dBwdHf39/cXFxVVWVmJhYQEBAUVERNTX19PR0XV1ddna2oKAgJSXl3NwceAAiIiIaGxszMzPFxMTk5OSys7NVVFTevXvn4+MTFBR0+/bt1tZWHh4eDQ0NLy8vMjKyly9ffv/99w4ODmVlZcCHvbOzE7if6+npHRwcFBQUeHp6fv/999XV1aqqqlpaWkNDQ7y8vCEhIfb29mZmZgcHB9LS0lpaWkDEfGlpiYGBgXQaTCAQbG1tYTDY+Pi4goKCgIBAZWUlDQ1NamoqAwPD4ODgxMSEkpJSfn7+1atXw8PDjYyMeHl52dnZQZ1sfn5eSkoqICAgMTHx3r17QMFYWlqak5Nze3t7d3eXnZ39zFwDiUQCV2Q0Gi0qKgp41sXFxaAOQgpvb28PDw8Igri5uWtqatbW1mhpaRUVFamoqDAYjJmZWVZWFnjhQxAkJiZ25lnd39/X0dHh5OTU1dWdnZ1VUlIqLCw8PT3FYDAODg5XrlxZX1+XkpIqLi6Oi4u7evVqQECAlpZWaWmppKRkfX39+vr6kydPTk5OQkJCREVFxcXFeXh4nJ2d9fX129vbHz9+DEFQcnKyurp6f38/KysrBEHZ2dni4uIwGOzj7viTkxM/Pz9TU9PHjx9ra2vz8PAQb/T09HRAiA4JCbG2tnZ2dpaRkYEgqKSk5MaNGxkZGeAWNzc3NzMzq6qqkpCQYGZmBr3FZ6Yb2dnZzs7O4uLihoaGy8vLXFxck5OTLS0t4uLiXl5ewOa6t7f3415SBAIBuNisrKxv377t7++HwWBoNPrOnTsga/PTTz9lZ2eDC7e4uEhLS7u3t9fX1wfodhkZGXt7e/b29mg0+saNG5mZmVlZWdLS0hAEFRUVSUlJubu7MzMzQxD09u3bp0+fenp6gnSDn5+foqJiQ0MDHA6HwWBIJJL4jfB4vL+/P2jhoaWlnZmZERISKioqAh0GL1++pKenJxAIR0dHLCwsZzJl/v7+ioqKEASBqRwEQSIiIi4uLrdv366oqJiamvri3mKAL48aJSUlV65cIf7Kx8dXUlKytLQEFH0VFBTi4+Pt7e0fPHiwu7traGgYGRkJQVBOTg4SiQSaoHA4nNiH097eDpTE7927p6urW11dXV9fv7y8zMLCAnIKVlZWwOIAhULJyMgAeUEdHZ3w8HAqKqrm5mYTExPwjCkrK0dGRmpqatrb24MdZWVlNTU1gSAwLy/vmcUzGo2Gw+EQBCkpKQEC6NDQ0Lt37xgYGE5OThYWFu7evZuTk0NOTp6WljY8PFxZWUlOTk6cF8jIyAQFBb18+fLu3bv19fWgK5SSkhKHwzU1Nd2+fRv0mBJhYmLy/Pnzo6MjExMTFxeXw8NDGhoaXl7ej9noRkZGYmJiOzs7zMzMubm5ExMTzMzMNjY2NDQ01dXVCwsLu7u7ampqenp6oM/lTLZ8aWmptLS0tLT0ypUr5eXl8vLy7u7uXl5eXFxcr169unjx4sLCgrCwMAqFysjIuHr1al9f39LS0uTkJBkZWUJCAhaLpaamnpycdHFxERISgsPhT548mZ6enpqaamhouHz58vT0dFRU1PPnz5ubmykoKOrq6iIiIoAErKura0JCQnJyMnEww8PDf/7znzEYDC0trby8vLq6OicnZ09Pz/z8fFpa2o8//tjY2GhgYKCgoJCamkpFRdXb2+vn52dgYODv709JSbmzs6Orq0tLSxsdHY3FYsXExBwcHCIiIkiVEw4PD5mYmExMTOBwOBsbW21t7Y0bN5qamsrKyh4+fPjixYtbt27FxcUpKCicO3eOlE8F2MaysrKzs7NXr15NS0traWl59OhRaWkpFRVVXFxceno6eL1dv349PT29sLDw4sWL4LJycnJevHjx8PCwq6vrxx9/TE5Ovnz5clhYGDjD/f39Pj4+T548KSwsvHfvXlFRUXBwsJ2dXWhoKBUV1cbGhoeHh5ycXFxcXFNTk46Ojra2NjFqHB8f8/Pzy8vLw+HwmzdvFhcX37p1C4FAbG9vP3jwIDc3V0NDQ0NDw9zc/LvvvjsjfQK4/9XV1Q4ODjw8PLu7u6ysrF5eXoaGhsbGxoGBgWdWNL8WXx41ZmdnqaioQAdHS0vLnTt3QkJCXr9+fe3aNSQS+d///d/BwcH6+vo//vjj27dvASH38PDwyZMnoGGMjY0tJCTk4cOHhYWFdXV1jY2NoNNZSUlJTEwM9HHX1tb+8MMPWVlZBAKBk5NTTEzM39//22+/jYqKcnNzk5OTe/z4cXBw8MWLF1++fOnk5MTMzFxeXs7Nza2rq5uVlXX//v2kpCQwqeHh4QHMfyBxTPwWu7u7UlJSdHR04+PjJSUljx49CgwMzMvLe/HixaVLlwoLC4uKis6dO5eUlGRsbKykpIREIsvKyiwsLBgYGMzMzCYmJkxMTKioqIqKisTFxeXk5GxtbYeHhw0MDFhYWPT19eno6M6kG9FoNB0dnZGREQqFAuUVHR0dJSWlj89wSkoKAwODp6cnExOTlZXV9PT0s2fP8vLyHB0dRUVFzc3Na2pqbGxsTExM4uLinj9/np6efoavraWlZWJiEhQUdHBwEBMTIy4uHhgYqKamZmBgoKOjMzIykpiYKCMjMzAwAEI5EonMz88XFRW1s7OLjY0FM6+8vDx9ff3+/n5dXV1NTc2EhISsrCxdXd2Kiore3l5TU9Pu7m4bGxsnJycHBwdzc3MMBtPW1kZNTU3alv7hwwdra2stLS07OzsMBvP27VtjY2MFBYWKioqFhQU5OTkfHx8kEuni4rKwsBASEgL6dzY3N2NiYszNzXE4XElJiYODQ3BwsLGxMQaD6enpuX//PunMnEAgZGZmWlpaolAoNze3pKQkCwuLmpoaLBZrYWExMzOTkJBgYmISERFhbW3d1NRE3HF1ddXa2hqJRBYWFpqbm4eHhy8vL1taWnZ1dbW3t5ubm6PRaPByDgwMxGAwYEjFxcUQBLW1tYE2+b29PU9PTy8vr9DQ0FevXk1MTFhaWpaUlBQUFABDjK6uLltb28TERKBXEBYW9v79eywWm52dXVpaam1tfaY9EoKg7u7uyMjIjo6OV69eJSYmRkZGlpeXHxwc5Ofn9/b2bm1tRUVFNTQ0lJSUnGlIOzw8TElJ6evr6+/vb29v39zcHB4exuFwh4eHTU1NLS0tXykQ9VV5jXfv3iEQiPDw8KampqioqKKiovn5+fj4+Pr6+qKiovDw8JycHBsbm/j4eDADnJmZqa6uNjExiYqKcnV1nZiYSEtLg8PhcXFxOzs7oA9taWnJw8PD0tKyuLi4tbU1NDS0vLz8w4cP6enpCQkJ8fHxUVFRKSkpkZGRb968ycjIKCoqys3Nra2tXVhYCA0NbWhoSElJSUpKOjw8rK+vDw4Obm1tPT097enpwWKxx8fHTU1NQFMD4ODgoKOjo7m5GWSw3717B073yMhIa2vr0NDQxMRER0fH1NTU8fFxfX3969evweS2tbW1qalpf39/dXUVJFB3d3erq6vBHOTw8BAcc2Fh4QyR7OjoaHp6mnQ1YWNj83HsBxXNubm5yclJILAMHNjBp+NwOCACsr+/v7e3B7KVu7u7Z1L0m5ubpIlJkPYnfZtBJEIvoIYFSNz7+/sH/wPof1QLIAgi1Qr4RYUYUJuor6/38vL6X2sTn7CA+ASTGuzV3t7+6ZraZ+LzCzEfb0k82/9n2B+fiX8Gy+vX+rl/4gj/xzA8PKyurq6jo/M1Eil/QPxfvV6/HwDP6F89is/F/0+5oX8QjI6Oenp6kopZ/Kvwn+f8n48z5/z3Y6z+5hf3P1Hjn4rj4+M/ZksSgUBYW1ubnJz8BOXxY+Dx+NnZWRwOBxYyx8fHw8PDU1NTBAJhf3+fyNAlEAjz8/PDw8Of1vVcWVnp7u4mkpr29/c/PQWbmJgAbcqfP+BfxObm5j8S9d3f36+oqPi4kExEWVkZMbdycnIyPT0Npgzz8/Otra1AZWNjY6O3t5eYqwYm6v9IV/nw8BDYCYGB5ebm5ufng/VaY2NjfHw8KA6sr6+np6cXFRWRBhqQqEpPTwfknYyMDF9fXyI/8DfEv03UODo6io2NJeX2DA0NAfmDT++4sbGBwWDOyB99/aLpYwAiExKJRKPRQK3nY7i4uOjq6n4ZjXJtbc3V1RXwX38P5OXl3b1794wwxP8K4N0LrsLh4aGamhojI+Pe3p6LiwspQ7e6uvqnn34CGcR/hN7eXkAGgSCIQCCAMvDHmxEIBNCtn5SU9MMPP5xRzfoCgML5L/7X/v7+06dPgWrRx8jLy+Pn5wccmby8PElJSRoamvX19bdv30pLSzs4OIiJibW3tysrK8NgMHJy8piYmMHBQXl5eWVlZTU1tY9vg7a2Nnl5+evXrzc3Nx8fH8vLy9vZ2dna2lpbW2dlZamrq4eFhfHy8k5MTBgbGzs5OYmIiMTGxhJ3t7e319TUNDExoaSk9PPzk5GRAXn0rzw/H+PfJmoA6V3Aie7o6Ghra+vv7//mm28AW+zTkJSUlJOTO/PHrKysMzzcrwR4o5KRkfHx8f2jd1dGRsbDhw9/rWgCSDHu7e0FBQWBV/HHN9zH4Y90DHt7e+Agh4eHu7u7YMoDXncEAgFkgsfGxh48eADO5+zs7PLyMrFRhaimAY4GGo4ODw9PTk6am5thMBgOhwPigxUVFU+ePNnZ2amvrwdU+vfv34MdOTg40tLSgGkeOA4OhyPOLABNlpOTEzyEp6en9fX1U1NTe3t78/PzxONDEHR0dCQoKOjv77+5uUlHR4fFYomMfjweD+z7iOdtZ2dnfHycuAZcXFzs7Ow8OTk5ODiYnp6emJiYn58HtXawfWtrK3FIx8fHra2toA5FPJMDAwNlZWXg3IqIiACFMTweX19fb25uzs3NTSAQ3NzcVFRUIAjS19dXUFCIiYnZ2dnx9/dnYWHR09MD5gOsrKwfs1p6e3tLSkq4uLiam5vfvXt3+/ZtCIJOTk4ePnwoLS0Nh8OXl5cNDQ0zMzP5+fkhCEpOTibqY4LzCWSNRUREgElVdHS0nJxcSEgIIHRsbm4mJCQkJCR85QTtq6LG0tJSUVERoLWvrq4WFBQA6ZrFxUVAWN7c3ARp/62trfX19aWlJfDAdHZ2guu0v7/f2dkJPErm5+cB4wMc/PT0FBRfAc2Gnp4+KSkJdBPr6OgoKipub2+zsbElJCQUFxcDssPa2lppaWlraytx2ra8vPzy5UtBQUF9ff3j4+PGxsagoKCJiQnQD6Ktrb24uFhfX+/m5tbU1ATu5ry8PC8vr7Gxse7u7qmpKaBVPTs7297e7u7uXl5evrCwEBsb6+PjExUVtbq6CpR7ifc0JyenhYXF0NCQk5OTi4uLnp4eaDxrb293cXGRkJDg4OAgEAidnZ02NjYGBgb19fVNTU26urrW1taamppAELSsrMzT09Pe3n54eDgxMVFFRcXW1jYjI0NHR2d4eDg7OxvwZefm5uLj4+Xl5Y2MjMTFxcEDj8ViZWVllZSUhISEgPhgZmamqamprq5ufHz869ev2djYuru7i4uLlZWVBwcHg4KCXFxcPD093717x8vLCxi3Dg4OqqqqoP7i5+fHx8enrq7OxMSUk5Pz4sULGRmZN2/eaGtrI5HI/v7+27dvy8vLs7Ozv3z5sra2FgxSSkqqra0tMjJSX1/fysqqq6tLQkKCh4dHTEzM0tLy+Pg4ODjY3d1dU1OzoqKiu7vbzc3N0tLy8uXLQEfz3bt3fHx8paWl/v7+dHR0ioqKLCwsoL44Pj5+8+ZNWlra/Px8BgYGJSUlVlZWFAq1ubnp5ubm6uqqqKgI7kkbGxtubm59fX1mZuaEhISGhgZ7e3tXV1d9ff34+Pj79+/T0tIC4fuoqKj5+XkDA4Po6GhxcfHi4mIcDmdubu7s7Hznzh3wuiYQCOBaAB5Nd3f3vXv3YDAYsbHw1atXRO4WKyvr8PCwpKSkvr4++F80Gm1sbCwuLg5WNIDBTPo0gdvv6OiIj4+vvr5+Zmbm5s2bYWFhcXFxgLD/8OFDcnJyd3f3pqYmNTU1cGWBWCkpgDMxWCgFBgZSUlKiUCgKCoqysjI9Pb3AwEABAQGgpPnF+PKosba2JiAg4O7ubmRk1NXVBQidgoKCcXFx0dHRf/7zn9vb29vb2wGpLjIy8ubNm0xMTF5eXkDgjJeXNy0tzcrKys7OTlZWNiMjQ1pa2szMDMwGNzY2zMzMgJCXlpbW27dvycjIODk5FxcX9/f3mZiYKCgocnJyeHh4NDU1VVRUREVFh4aGZGRk/Pz8gNw2BEGNjY1aWlpoNJqRkdHCwmJ6ehqBQGhrawMmKD09vYCAABiboaHho0ePgIJebGzsX//61+7ubk5OTl9f3/r6ellZ2czMTD4+vrKyMioqqrCwMAYGBk5OzqioKFFR0aSkJCsrK2LIZ2dnt7Ky6unp+e6779zd3dXV1UVERKqqqp49e9bT0+Pp6fnkyZO3b98yMDBkZGQkJyfT0dElJyf//e9/DwwMNDIyEhERycvLo6SkfPnyJQcHh5CQEC0tLeAIZGdnf/fdd+Xl5UDikJycPCgoqLGx8c9//nNTU5OSkhJgLu7s7FBTU9vb2xcUFNDR0VVVVdHQ0NTU1ExNTQGiGjMzc1FRUVpaGtDIhcFgUVFRP//8M7jbent76enp4XB4REQEiMXp6ek3btyYmJh48eIFHR0dBoOho6Pb3t5WVlZWUlIaGxujpaXt6uoCMoupqanm5uaHh4e8vLyAUiUrKxsdHT01NcXHxxcZGdnX13fnzp3w8PDbt2+j0WgGBgY+Pj4FBYXi4mKgowlWJQcHB4yMjDk5OXl5efT09Jubm9ra2oCnd3BwICoqmpeX9/79e2pqaiwWW1RUREtLi0Khbt68GRAQQElJGRwcDEFQaGgoCwvL1tZWdHQ0Dw8PGxubrKxscHAwFxcXOC3h4eFTU1Py8vIuLi5mZmaARhgeHs7MzKylpQUEhx0dHY2NjSEIWlhYoKSkzM/PhyCIhYUFhUJpaWlFRUURW72Tk5PFxcWBS4a2tjZYawQFBUEQ1NnZaWxsvLq6Ki8vD/STpKSkioqKPnz4gEAgVFVVX7x4Ae6f7e1tPj4+IF6bkZFhamoqJSXFzMyMQqHQaHRERAQnJ6eTk5O6ujoEQbm5uYKCgmcezOzsbGFhYRA13N3dgZ6zuLg4AoGgoqJKS0tzcXH5yjbcL48aCwsLbGxsYmJi2dnZoEcIgqDo6Gg2NraOjo4LFy6AHNL58+czMzMbGhru3r07MDAQHh4OCMLj4+OSkpKMjIyFhYXi4uKAK+Xo6AhWDTk5OXfv3oUgCIfDUVBQNDU1cXNzg95BAoGgq6urr6+Px+OZmJjA7IaBgcHKyuratWuhoaGqqqqAJKqpqQn62dBotJaW1urqamJiooGBwa1btw4PD6WlpUGHEiD/3Lp1C1At9vf3ubi47O3tOTk55eXlUShUa2srCoWipKREo9FWVladnZ2CgoLV1dVHR0eXLl3S0dFxcXEhMsfY2dltbW23t7fv3LkD6Mzs7Oyurq6SkpIQBLW3t/Pz8+fl5V2/fn1+fh6w1yIjI7m4uICbiZiYmK6u7rfffhsaGhodHd3c3Ozn5/fkyRMVFRXA425ubvbw8AgICGBkZPTw8FhbW3v06NHp6am/vz+YFUMQRE1NXVxcvLGxISgoGBERcfXqVTAVunz5cnFxcUZGBgwGs7a23tzc5OHhYWdnr66uxuFwQ0NDXFxcg4ODgKcIHi0IgioqKoBic3Nz89OnT+Pi4nh4eCAIMjEx8fX1xeFwIGI2NDQ8e/assrJSSkrq4OBASUkpNTW1u7vb1tb29u3bOTk5oqKitbW1S0tL1NTUlpaWZGRkGRkZWCy2vb2dhoYGMFbo6elDQkLAtwBHa21tBeLa9vb2UlJS4AYQFhaurq7+8OHDw4cPd3d3R0ZGWFlZjY2Nf/755+rqaqCNCEFQcnIyIKdnZ2erq6uD2WV7e/vY2Bgej+fg4AD9kDo6Ol5eXnp6epqamhAE5ebmcnBwqKioeHl5QRBkZmYG7qL5+XnAFocgSEJCIjAwUFNTk3SRm5aWRtrf8eLFC25u7o2Njba2NllZ2Y6OjrW1NTgc7uHhcXJyAoPB3r9/f3BwEBIS4u7uTqRpHRwccHJy1tbWgl/X19eVlJTS0tIUFBQAnUxLS8vNzY2bmxsoldrY2KytrZE6pMTGxvLw8IBAZmhoCJZXTExM7u7u1NTU8fHxOBzuX8YoX11dzczM9Pf35+fnFxMTY2RkJBAIkZGRCgoKHR0d586dq6qq2t/f/+677/Ly8ubm5nh5eSEISklJuX//PjgCHA6/f/9+VVXVu3fvsFhsWlqasbExOzv7/v5+aWkpBQXF/v7+8vIyMzNzZ2cnNzc3kWtoZmYGh8PxeDwtLS1wQqShobGzs7t69SqQigXrIH19fRERkZ2dHRkZGbCeFBISyszM/O6777a2toSEhNzc3HJych4/flxaWnrp0iViSszCwuLcuXOgpYWbmxuCoNDQ0Pv37+NwuPn5+eXl5QcPHiQmJp6cnDAyMtrb28/Pzy8uLhIIhIODg7t372poaOBwuB9++KGysjIxMZGKiioyMpKCgqK4uNjU1JSGhqajo4OSkjIkJKSyslJAQCAvL+/ChQvl5eXl5eWgxeD69euxsbFNTU2FhYXe3t5gjpOZmXn37t3w8HBKSkokEklJSamvr5+Xl3fp0qWlpSVvb28YDHZ6erq4uHju3Lng4OCZmRl6evq8vDwwyOzsbCEhoaWlpb29vUuXLoFZd1RUFB0dXUxMTEpKCmgRiImJsbW1raioEBcXB2oXVVVVFBQU/v7+ZmZmtbW1g4ODd+7csbGxoaOjU1dX7+zspKCgcHZ2trOzq6qqApOI9vZ2Xl5ea2trAwMD4C0SEhJCT0+PRqMnJiZu3Ljh4+MjJiZmZmYWGhpaX19vbGzMzMysr6//zTffgAnF2NgYBQUFHA43NjamoKCYm5uzsrKio6MDuRgNDQ0YDBYQEHD58uXy8vKGhgYKCorExEQeHh4kEhkREQEKDZmZmWBKb2lp2dfXFxsb++TJk8DAwNDQ0JKSkp9++ikwMHB1dVVAQEBGRqayspKDgyMoKEhTU7OkpKSxsRH0mNDS0goJCYHHDI1G8/Ly+vr6mpub19fXMzExqaurA54l6EiipKRMSEg4ODjw8vJSU1Pr6upaW1tjZma+fPkyIyMjBwdHYmKiuLi4srIyCEmk2NnZwePxHh4eV69elZOTW11dLS0tBTYu4LtISkpaWVl5eXltbm46OztLSkqam5vPzs4mJCTY2dmBg2xubhoYGDx9+rSzs3NjY0NWVlZSUnJlZUVdXd3X1zc7O1tJScnR0fHX5rzP4MujRk9Pj6SkJDBo6OrqEhQUNDAw0NXV7e3tPTo6ev78ORcXl4qKCjk5uaenp6enJzU19eDg4NjYGCsrq5SUVHR0NHhIADE+MDAQpJ1tbW2Pjo4ODw8NDQ3l5OQsLS3RaHR7ezsFBQUKhQIJi6CgoDt37iCRSCoqKjQaPTk5yc3NHRYWpqurKy4urqOjU19fD0FQX18fKyurhIQEGFt8fLysrKyRkRETE1NHR0dKSsqTJ0+QSKSwsDBQmgfTWgiCampqgOtaREQESM5tbm7q6uqKioo6Ozs3NDQoKyt7eHgcHBw0NjYKCgqqqqqCKSUWi1VQUNDX1w8ICJCVlU1PT29ra1NQUMBisSEhIerq6j4+PsrKyi0tLXV1dUAS+d27d4WFhTIyMkVFRW/fvjUxMZmYmGhqapKTk3NwcOjq6oLD4UZGRuA+dnR0zM3NDQsLc3BwiIuL8/f3Dw4OdnFx6e7u7u7udnd3X11dff/+vbOzc2xs7M7OTnBwcENDw9TUFAqFwmAwxHJDbW0tWI7h8fjU1FQbG5uKior6+nokEtnW1paRkeHl5VVVVQW0zurr68GzR5T/qaio8Pf3b2pqKi0t3djYqKys9PHxAVPL5ubm7OzswcFBMODXr18HBAR0dnYuLCzk5ubW1NQcHR2Vl5e/e/dud3c3IiIiIiJifX39+Pg4Ly+vrKyssbER2ErNzMzk5ORk/Q/m5uampqYKCgpATndycjI3Nxd0SGKx2IODA5BvWl1dTUlJqaurA9nKrKwsBgaGV69eEZNl7e3tr169evv27cjISEFBQVNT0+bm5ps3b96/f396ejoyMpKTk0Osf/X19ZWVlU1PT4+PjxMVPRsbGwsKCgAlF4fDAZo2BEF7e3vDw8Pv378fHR09OTkZGBgAGcf9/X2g54zD4UZGRkCSsr+//2NqRk5Ozu7u7vDw8Pj4+MDAwIcPH+bm5kjd+aampvr6+og7Dg4OgoC1tbUFfgDvrZWVlZWVlbW1tYODg9XV1bW1tQ8fPhwfH4Nt1tfXgaLy11QPvzxqHB0ddXd3NzQ0gNry+vp6bW0t0QZif3+/paWlt7d3ZGSkqakpLy+PmFSfnp5OSUmprq4mEAg4HC45ORkQ4wEhn8iQOz4+LikpAc///J2QArYAACAASURBVPx8S0vL0NAQYDp8+PCht7e3v7+/q6sLdJQuLy8vLy/j8fjW1tbBwUGitN/S0tLbt29PT0/X19dPT083NjbA9QZXFJCyd3Z2dnd3T09PSUvov8i3+bjBDIzz6ykDf1gQCITY2FgKCorfQyz78PDwK6fKn8Dp6ampqSnwWPmdPuI3BIFAWF5ePkPk+bRB/L8Q/+zK61fyI35x9//wGn8/4PH4ly9famhoNDY2/uYHPz09/Upjjk/gw4cP/v7+tra2Xy9d9U/AL97DX6mr+Pvh34av8R/8a/EH5LP+B/8q/AZR4+tlZv8DCIKAR9Fnbnx6ejoxMdHb2/sFLU8LCwv5+fm/aNT2a7G5ufmPeq6JL09QQftVh+3p6XFzcwOMnk/g+Pj4xYsXgYGB//y+r8HBwYCAgLCwsPDw8LCwsIiICAQCYWtr+7vG1r29PWNjY19f39/vIz4TXxs1PDw8QF3qV2FsbAyFQgFG06cBvIinpqa+aHR/XExPT5PafEEQVFxcTCr8AUEQHo/v6+sjlTgn/S8tLS0GBgbSh3ZsbOxjgzhSjI6ODg4O9vb2gmLT130DCIKg4ODgwMDAT2yQkJAgJydHKmbxOWhoaPj2228BM+LTUFNTu3Xr1hdHjcnJyfj4+M/Uvif9NTIyUlFR0cbG5rvvvsNgMDIyMhISEqQiVb8TjIyMACv0X4uvihoZGRmamppfUMWZmZm5evUq4GJ9Gi9fvvz2228/0T70aYyNjVlYWHx6G9J7Djgbkq63T05Ojo+PwZzoDI+bqHh85sEmtmyBLCkxxQ1B0MzMDMj/KSkpAWnZw8NDYDU4MjJCrNJPTEwsLCzMzc2xs7MDIsPm5mZvby8xJTk6Ours7Pzw4UPSj7ayspKTkwOvu4GBgY/X89bW1goKCru7uzAYLDw8nOijsbe319bWRqqFjcfjp6enR0dHgZQxkCMG32JmZqa4uHhubu7o6KixsXFkZGR1dfXdu3c9PT3d3d2kNPbd3V1ubm6g4TY1NZWZmTk9Pb25uTk0NNTe3p6ZmbmyspKTk1NZWQn46QUFBRkZGbu7ux8+fODh4QGF9tra2szMzDP55omJibi4uK6ursrKSlZW1piYmPz8/JOTk5OTk5aWlpcvXwLvxZqamrKysoqKipWVldTUVGKuva2tLTQ0tL29PTs7+/79+93d3UdHR/n5+ampqVtbW319fYWFhQUFBf39/R0dHd7e3g0NDWeamBYWFra3t1taWm7durWwsAAYxjAYDIPBREdHg7NaW1vr4+NzJmK2tra6urqmpqZubGzExcU5Ojr29/fv7u7GxMQEBgYiEIjk5OTCwkIrK6ve3t6ZmRlvb29/f38HBwdvb+/T09O4uDhRUVEIgpqbm11dXePj44m3xPr6ur29vb+///z8fEFBwcrKSnR0dEBAQGtrq7W1tZqa2ujoKPCs1dLS+tiQ+Ffhy6MGgUAQFRVVUVE5ODiYnZ1Fo9HJyckbGxuvXr3CYDBoNNrPz29ycrK0tDQ3N/fw8PD4+LisrCwlJQVUIhQVFUE3XmVlZVJSEqgwETE7Owt0k4aHh9nZ2cPCwkJCQubn54+Pj7Ozs4EPK9AyioqKQqFQExMToaGhgBYNQRA4U8B69/z58+AkxsTEeHl5NTQ0vHr1Co1GOzo6lpaWZmRkmJmZEZl5EAQBVa7a2tqampq6urrh4WEVFZWBgYGSkhJHR0cnJ6eWlhZ7e3s4HA5Ugv39/YEQE3G11dTUpKioKCcnZ2pqWllZ6e7ubmhoWF1dnZiYaG1tbWZmVlpaeuvWLRYWFgwGIy4u/vz5c2lpaSMjI09Pz62tLSQSCaSMvb29r1y5oqys3NjYCHjQOjo6Y2NjgYGBlpaWjIyMgDQJPhTQMe/cuVNXVxcbG6upqSklJWVpaUm8q7a2th4/fgwo2/z8/Pz8/E+fPlVTU1tYWDA3N7ewsGBmZiZG59PTU6BzraioCKiiHBwcOjo6s7OzHh4e5ubmjx496unp4eTkDAgIqKmp+e677+BwOBMTk7m5OfEBe/PmzcWLF2VkZMrLy5WVle3s7ADr/MqVK2pqaoKCgszMzEZGRuTk5A0NDTU1NSYmJiwsLEC3UVFRcWhoKCwszMbGxszMTFJSkhjcu7u7FRUVbW1tFRQU2tra7ty5Y25uTk9PHxERMTU15erqqq2traCgMDIycufOnXv37tnY2GRkZCCRyBs3bmRlZRUWFmppaaFQKDgc7ufnd/HiRXd3d7C+kJWVVVBQQCKR33zzzdOnT4F8npeXl7e3N2kJifgFsVgsFRUV6ILBYrE3btxAIpHc3NxoNDo9PR2oGV68eJHYbzI8PAz0n6OiosrLy728vFRVVR8/frywsACDwbi4uCIjI//2t79ZWVmZmJgICQlNTk5ev35dTEwsLi6OiYkpODgY0G27urqEhYUzMzMZGBjS0tKIl0xJSUlJSamvr++vf/1rV1eXnZ3dixcvampqIiIigE89Eonk4uLKyMj4ytz2l0eN/f19Hh4eHh6eyspKISGhV69ePXv2zNXVVURE5MGDBy9evHj8+DE1NbWLi8ujR4/8/PwGBga8vb3l5eWfPn1KIBCMjY1bWlowGIy9vb2jo6OQkBCxQtbe3q6goBAaGqqlpYXFYnl5ee3s7EDvycjISHR0tJSUFA8Pz9LSEgcHx7Vr17S1tYuKipKSkmAwmLS0dFVVlZycXE1NjZ6enrOz89WrV/Pz87W0tAwNDSMiIpiYmMzMzH744Qd3d3d3d3cODo7Y2FjSWc/g4OD333/f2NjIz88vLCzc3d2trKxcVVVFRkYWHx9/+/ZtOByupqbGysqampoqLCyspaXl4+Nz8eJFYqZgdXX1woUL5ubmhYWFtLS0Pj4+enp6jIyMoAExISGhq6sLcIQHBwdv3Lihq6vb0dFhbGysoqKCRqN1dHQ2NzdramqSk5OZmZlLSkokJSVFRUUDAwNpaGgUFRVVVVX39/cTEhKYmZmJy5zT01NZWVlbW9vu7m4WFpbZ2dm5ublLly4RyYuHh4d6enpAAYiDgyM9PX1ycvLp06f29vYUFBSpqalMTEzR0dHE8xAfH8/FxXV8fCwpKenj49PW1sbJyTk5OVlZWYnBYL7//vvm5mZ9fX0UCrW6uvrzzz8PDg7W1dU9evSIeB2B7GtmZqahoSEMBsvJyREUFCwtLeXm5u7s7GxpaaGhoYEgCAaDubi49PX1JSYmcnBwgA4LDQ0N0Onn4uLi4uLy9OlT4nRDXl4ejHNzc7O6uhqwB93c3GRlZVdWVtLS0vT19R8+fAhBkKysrL+//9HRUUVFRUxMzJUrVzw8PMTExADJeHt7OycnR0REpLe3969//auLi4ujo6OVlRUIgjMzM/Pz86KiohISEj4+Pr+YsKisrKSkpAR+FO3t7UBPODAwUEtLS0pKioODIzIyUlxcnCinvrm5qaGhwc3N7eLi0t7eHhoaqqysfPPmzZWVFRcXFxQKBUEQCwvLmzdvOjs72dnZIQji4+MDXa1IJFJOTi48PFxXV9fPz+/mzZseHh5IJJJUmK6qqoqNjc3Q0FBUVFRYWBiBQBwcHCQkJBgaGgoKCjo4OLx580ZRUZGfn5/0Qn8BvmqFoq6uHhgYWF1dfeHChYSEBGNj47S0NG1tbR0dHQiCoqOjHz16BEGQi4uLgoLC7OwsBoMREREhIyPD4/HGxsaZmZkPHjzQ0dGxtbU1NzcnTm719PQUFBQgCDo9PV1YWAAtVZ2dnQ8fPhwfHw8PD9fU1AT9Bbq6uoBR39jYiEQiRUREpKWlEQiErq4uOFRdXR0bGxsEQY8ePVJQUEhPT09KSqqoqHj27NnJycn6+jpgGdrZ2ZHOgeFwOCMjo7GxMRsbm5KSUn9/f1VV1blz56KjowsLC3E4nK2tLfhccnJyQNCqr68nFYNgZ2fv7e2dnZ29fPkyEHdsa2tra2vT0tJiZWUFku4gs8DExASkYgMDA/X19c3MzIgdluPj4xwcHIuLiyIiIoKCgiUlJcPDw0ZGRoAlHRkZSUNDQ7oigMPhPj4+OBzu7t27YEJHRUUFaMgACAQCKFZzcHCUlZV9+PBBXFxcUlLy9u3bzc3NTU1NpK7r4eHhgBerra2dkpLS39/Px8eXlpYmJiYWERFx+fLl9vZ2Q0NDDw+P/f19amrqgYEBINJLXNzt7e0xMjKmpKQYGho+e/ZscHBwampqe3ubnp6+s7Ozrq6OiYkJgiAeHh4bGxs4HA6Hw+Xk5MClFxAQCAgIoKenBxNJousNBEEKCgo6OjoHBwdHR0dFRUXg6XJwcFBUVPTz81NQUIiKiqKmpj45OREUFHzx4sXm5iYVFRXQi0YgEHJycmZmZnt7e4eHh8XFxTAYrL29/cqVK/7+/mNjY7u7uw0NDefOnVtfXx8cHARtSj///DMOh/s495yZmfn3v/8dMIbS09PPnz9/dHSERCLV1NTMzMy4uLhwOBypMWhPT09UVFRWVhYzM7OgoKC0tLSfn99PP/00MDAgKChobGy8trZ2+/btysrKysrKBw8e7O3tCQgIqKurj4+PS0tLFxcXo1Ao4F9BQ0MzMDAwPDxMqodyenpKTU2tqqo6Njb2zTffREREQBB0//59NTU1ISEhJSWl7OzshoYGW1tbwJ3/YnzVCkVaWtrV1bWtre3HH3+sqqqamZlZXV0VFRWVl5fH4/FOTk7Xr18/OjoC83lzc3MrK6uoqKhr167h8XhhYeHg4GAYDGZjY7O4uLiwsEA8uTY2Nvfv39/Y2Dg+PsbhcA8ePMBisY2NjXfv3vXy8mJiYgoLC6Omph4bGwMcTQKBwM3NraSkZGRkxM7OHhwczM3NjcVigcECOTl5V1eXrKyslJRUZ2fn8PBwVlYWNTX16urqmzdvysvL09PTqaioiPw0CIKioqLOnTv35s0bXV1dMjIyCIIGBwcvX74cExMDxETl5OSUlJSOj4/Nzc1ZWVmLi4tJJYUXFhZ+/PFHNBoN2g00NDSA+QMajS4rKwOi/iIiIhISEtnZ2VevXjU2Nj46OrK0tGRgYEhPT79586aNjc2LFy+Gh4eZmZktLCxAP1VCQkJOTk5DQwMdHR0SiRQQELh48SJpxsfX15eMjKy5udnIyEhFRQWsdEipa8HBwdevXw8PDycjI0MgEH19fdeuXfP19RUVFTUxMbG3tyeuEw8PD6WkpC5evFhXVycqKurh4TE0NCQkJIREIh8+fGhra8vOzg5mjmpqapGRkVRUVCCD8OjRI6J6e09PDy0tLQKBaG9vh8FgWlpaoaGhhYWFDx48wGAwnp6ed+7cGRwcNDExUVNTc3d3FxISkpSU5OPjS09Pp6Oji4+PT0pKEhcX9/T0TEtLI94evb29MBjMyMgoISHB1dX13r17i4uLQG8ZhULBYDArK6tnz57FxMSwsLAYGhqOj49LSUnp6Og8f/7cyMiopqaGj49PS0srOjr6/fv3HBwc4eHhaWlp3Nzc4L3i4+Nz+/btkpKS1tZWUVFRd3d3DAZTW1uroqJCSrs6ODjw9/dnZWUFkvdRUVG8vLwgJ/L/2HvrsCrTrn2Y551+5lFn7LEFlRIQQUpCGgEFFJBGutmkm5ZGBKS7WxqkRelNN9LdIQ2b2sD9+2Md731wqOM4OvW933P+Rew79h3ruq61znWe2traVVVVsrKykpKSjx49QmNxW1ubqKgoBoOJiIhITk4GPyTwDJKXl9fR0QkLC+Pm5vb19YVWzIqKivv3758/f97Q0BDGGAMDA2Vl5cHBQV9fX0lJSQMDg3dy6s+fP4fW59DQUJj8xsXFqampgRJyRkaGkZGRq6vrF4qSfH7UAE8wUVHRsbGxp0+fCgsLGxsbv3jxQkRE5O7du7m5uffv32dhYamvrw8KCuLm5tbT0+Pl5VVRUaGnpw8ODr5+/bqtrW1OTg4XF5ecnJyXlxc6mMzOzkpISECXXlRU1M2bN8PDw1taWmDFePv2bXNzcwEBAQwGIyQkJCoq2t/fHxQUxMfHZ2VlJS4uXlNT4+joKCws7OrqOjk5KS8vb29v39nZqaSkJCsrGxsbC9O84uLihoYG4Pa/I9IxMDAQHBy8t7dXWVmJpjwKCgrU1NSePHkC+w8ODgau7tOnTzU1NfcrJnV3d3t4eIBi+Pj4uI2NjYWFRXt7e2JiIiRTEASpra11c3N7/vy5r69vYmLi2tpaXl6em5vb1NRUXV2do6NjbGzs+vp6RUUFSDHn5+fb2tpCaq2qqsrDw6O2traurm5/sFtaWiorKxsfH9/Z2cnOzk5PT38nfQsJvNra2oqKisbGxuXl5erqauisgT6xra0ttF+7vr6+srKyvb29v7+/vb19Y2NjYGBgcnKysbGxr6/v7du3LS0tPT093d3dLS0tIKKxvr7+5s0b6KTa29ubmprq6emBCfzs7GxJScnY2Njbt297e3t7enoGBgZ6enpmZmYWFxeHhobW19d7e3vn5+cHBwe7urr6+/uhcDY0NNTc3IymbwCLi4vNzc0zMzPj4+MgEba+vt7f34/H44eGhlZWVubm5mAnHR0di4uLKysrw8PDoKkBm7e0tIAKNCiJIAgCamO7u7uDg4NjY2MwWevr64O0BYFAACYxip2dncXFxfn5eZilgjIzzDdhjba9vd3f3w+3YGlpCSYFq6uraBCBSRnonkEXxfr6OqrwTCAQtra2aGlpTUxM0IPuZyr8jTqjnx810AoC/Pr27dulpSU0UYSODLu7u+vr60NDQ5ubmyBssbCwMDs7OzAwAGIts7OzLS0t7xOW+/r6lpeXP+JgDFdtb2/vg/8Fue33//jOzyAF/nu/O+A3N/wvafWfgL+dl726utrf3/9rkn8fQW1t7cGDB4WEhPZvC2W+P/QEfzf+yw39L/6Lfyjm5+fHxsYGBgb2hwk8Hv/OzOuvx3+jxv8d/GOnNjDpAz7FBz+w36bwrzutT8be3h6YznzGogCPx4+NjaEts5+HhYWFvr6+9fX137UTaPIcGhr6w6/q//eiBoFAmJqa+l3zvd3d3Y6Ojv0Fgl/DB51yGhsb0foWyEa/75n+QdTV1UVFRf1lHbF7e3sJCQl+fn6ZmZlpaWlhYWFeXl7GxsZfKKbwh6Cjo+POnTv79Yf3Y29vLzs7OyYm5h8b+NLS0ujo6D6D5lBRUXHu3Ln95pXz8/OfIgS//1Lk5+cfOXIEJQG+/4Hp6en9JuTLy8ttbW1Q+baxsXn/81+If1zUqKysdHZ2/sg3xOFw1NTUv0uvfWlpiZ2dHVUueR8EAqGzs/PXWqpVVVV5eXnh54mJCVJS0sePH3/8iKBqkZ2dferUqT/Q7iQyMhKkA34NYmJilpaWtLS0kpKSwJ25dOnSp1CzPxFubm5hYWEf/FdZWRnY5X4QIPYN2rwfREpKClQK/zJ8kOn7PlCTATIysvj4eARBdnZ2IDMKvGEEQba3t6GUC5/cv6CYmJhgZmYGAVf4771799BBaG5u7p1HHY/H9/f3Q1Z1dXUVYsH29va1a9dAwwU00NEPt7a2bmxsREdH79fT9vPzA+K5ubm5qalpZ2cnOsr29PTAPv8efQ30wBsbG/DDzs4OWGAQCATgZX98883NTfRW7e3twWqts7MzKysLUsqbm5tbW1voywzs6b29PU5OzsDAQPAoXF9fB72M/XlZtLA0MTEBN9jS0hKtUaN+EwiC9Pf3z87Ojo6O3rx5E/TgFhYWBgYG0Px2Q0ODubn5fnVGdXV1TU3Npqamt2/fwtRxbW1tdnYWh8MB55pAIBw5csTJyWlmZoaDgyM6Orq4uBie0YWFhby8PEjLo7etoqIiNja2tLR0cXERh8MNDAyAHyfUQYuLi58+fVpdXb2zs8PMzGxoaDg/P19XV+fs7Pz+0AescC4uLij9DA4O3r59G6T6oOtneno6ICAgKChof8UuPz/f09PT3d29rq4uOzs7Nzd3YWHB19cXHq/k5GR9ff3o6GgCgcDIyCgpKdnf35+Zmamurh4REYF+CwcHh3/961+5ubkTExPW1tZmZmYgR/7s2TMVFZWKigonJyc4mdjY2J2dHQ8PD1NTU3V1dScnp6mpqadPnwL5qqqqCsxrk5OTc3Nz7e3tJycn3dzcgOyUnZ1tbGzs4OAA79X09LS6ujoWi3379m1kZOTs7Kyfn9+jR49wOJyVlRWIxU5OTj558kRZWRm1xcTj8Z6ennp6eu7u7g0NDVB1lpCQ8Pb2hjIwqP4oKysbGRndvn0b3nl+fv7i4uLBwUEMBqOiouLm5gbVaA8Pj5mZGS4urpSUlBcvXlhaWqqqqra2tg4MDNjY2GhoaEDNHg5dXV39008/ycvL9/X1OTs76+rqysvLo24VtbW1ioqKioqKAQEBPT09WCxWS0vLxMRkY2ODl5e3ubn59evXtra2ampqAQEBDQ0NGhoaQkJCbm5uGhoa586dg6F0Z2dHQUHh5MmT8fHxoaGhQO0VEREZGRkJCwtzcnJSUFDY76r9Gfj8qLG6uqqnp6ekpCQvLy8pKTkyMmJra+vj4zM9PS0sLOzm5jY3N4fFYi0tLY2MjIB45+7urq+vD0NKUVHRo0ePNDU1odPBw8NDQ0MjIyMjJCTEx8cnKyuLn5+/oqKiqKhIWFi4v78/Li7O2tra2Nh4YmJCXl4+Nzf38ePHkpKSExMTurq6tra2EPUzMjJ0dHSAwV1SUoLFYkVERLKysp48eaKlpbW0tPT06VMdHR0pKamuri5PT09lZWV+fv7k5OTDhw8bGhqWlpaqqKioqanJy8u3trba2toaGhpev359f8uQlpbW5cuXVVRU2NnZQ0JCLly4kJycnJSURENDMzg4iCDI4ODgzz//zMfHl5+ff+PGDQkJCagKd3V1SUpKurq6UlFRQRvo7u6up6entra2gYHBiRMngJNib28/Pj5+5cqVgICAkJAQRUVFT09PKiqq8PBwSkpKLi6ugoICR0dHU1PT06dP19TUvH9rODk5ocllb2+Pg4NDUFDQysoKVLPl5eW9vLwkJCTQnkM3NzdlZeXs7Oxjx449f/5cUlKSm5t7YWGBnJw8KioqISFBVlYWh8Nxc3O7uLiwsLCIiYm9fv06NjYWi8WSkJDAE7+3t2dubn7ixIm0tDQhISFfX19tbW0ODg4TExMgUCclJdna2vLx8cXFxVFSUlZXV9+5c4eMjCw2Nvbnn38uLCxUUlJSUFDIz88XFhZua2sTFBTU1tZOS0ujoqJaWFiQkZERExMrLS1lYGCIi4u7ePEisBu3trZkZGQEBQUrKiqIiIjy8/Pt7e1tbGwKCgqysrKAWgoDb3h4OMqpMTMzY2Fhyc7OJicnj46Ovnz5soODg42NzZEjR0pKShgZGZ2cnAoLC4mIiCIjI3Nzc0+fPl1bWyslJVVeXs7Ly+vn5zcxMXH58uX4+HgVFRVxcfHJyUkBAYH09HTQjqamphYREZGQkEhJSRkfH79x4wb6lvb29tLQ0GRkZBgbG5uYmMzMzAgJCSkoKMB/HR0dT5065enpWVpaKigoeO/evcDAwJ9++qmiokJCQgKHw129etXCwsLW1paUlJSDgyMlJWVkZKSoqMjGxkZdXR1KyHt7e5aWloKCgtPT0+Hh4Q8fPlxdXWViYrK3t7927ZqNjY2CgsLDhw8/+8VHviRqbG9vy8rK8vDw1NTU8PPzy8nJaWtra2lpbWxsnD59GhoH7t27d+HCBU9Pz6dPnx47dszY2Dg3N5eUlNTV1VVMTKy5udnNzY2dnV1bW5udnT0+Pj49Pd3R0ZGGhmZ4eJiEhCQrKyszM/Px48fR0dH09PRxcXEnT54MCAhQUVHp7e1NSkqioKCYmppSVlZG22dFRUX5+PgSExNTUlJISEiSk5M1NTWlpKTs7OwsLS2jo6PJycnz8vLIycnp6OiAKAmqc9euXSsrK5OUlOTn5/fz86OmphYWFtbU1EQQxN/ff3/UUFJSAn1ANjY2c3NzKSkpV1fX8PBwdCGwubnJxsaWlpYGC8uhoaEXL14ICQlZWFgcP348MDCQiooK2gc6OjouXLgANeYrV67Mz88LCAiA6TEbG1tAQAAXFxco/V+/fl1LSwv4JgiCJCQk2NnZffXVVyB++w6AxIkgyPr6Og8PD7wtTExMvr6+R48ehREeCKmrq6tXr16FQZ6RkRGs3kHdF0hZvLy80Jqtr68vLi6uqKgIuQnodaagoABmJIIgcXFxPDw8y8vL//73vy0tLZ2dnVVUVC5evIgOpAoKCqD6zcDAUFZWZmRkJCUlBb++evUqICBAX19fVlYWmK9mZmaGhoZFRUWgMKyvry8lJWVvb3/p0iU/Pz8zM7P6+nqY5hQUFFy5csXIyEhMTIyHh8fa2np5eTk+Ph6LxXJwcJibm4+MjAgICNy5cwftG7h58yYZGVlYWFh0dPTAwAAos5eUlAA5XUZGRklJqb+/n56eHjgjoEssLi6elJR04sQJWCTy8PA4OTk1NjZev35dW1s7NTU1Kyvr0KFD4eHhz58/T0hIuHHjBogJsrKyolFjfHyck5NzaGiIj48P/ujs7MzPzw/fZWBgwMnJiYGBAYPBUFFRKSoqtrS0NDU1rays8PPzp6amQqtLXV1dWVkZDQ0Nmunw8/OzsrJCHwBbW1u4tubm5qDDysrKqqamdvbsWVAb3t+p+Bn4ohWKp6dnQEAAgiDPnj2Tk5MzMzOD3AGocsNJgzY3nDcsAcTExKipqe/evYsgyMzMDCMj4/Pnz7W0tED5vri4+ObNmwiC2Nvb8/HxYTCY+fl5e3v7I0eOBAYGhoeHDw0NSUlJ5eXl7ezs3Lp1S1FREQj8gPLyciMjIx4enocPHx48ePDRo0e5ubk9PT3Ozs4wFTp16lRhYWFpaSkfHx/IwyMIMjQ0xMbG1t3dzc/PLyMjk52d3dDQoK6uDoOAiAW8ZwAAIABJREFUq6vrfq8aRUVFc3NzBEF4eHjCwsIKCwsvXryoqKi4v0Bw6tSp8PDwubk5RkbGiYmJ1NRURkZGAwMDMjKyhoaG5uZmIBHU19cfPny4srKyu7ubmJh4fn6elZXV0dFxaWmJlJQ0OTmZj4/P2dl5Z2fnxo0bwMX08vLKycm5ePFiZWXlv/71LxDF3K8kQCAQGBgYrKys9vb2YJDJzMycnZ09c+YMaPnFxsYCPwpBEDwez8bG9vDhw4GBgfPnz7e1tVlZWTEwMPT09Fy8eBE8KHh5eefn52VlZf38/MTExMBT4/Dhw3FxccePH0cZ615eXocOHSovL6eiosJisd3d3fX19ZSUlBoaGj09PaOjozw8PLq6uvPz86dPn05ISJCTk+Pl5d3Z2Tly5EhcXJyxsbGoqKi7uzsxMXFaWhoPD4+FhUVJSQkxMXFycjIFBYWgoGBeXt7Jkyejo6PLy8sXFhbgTZufnz906JC0tPTk5OT3339vYWGBIMjNmzc1NTVv374tKyubm5tbVFRkaWkJXHUEQQwNDUlISDIzM1+9etXY2AjZyoSEhMuXL6+srIBHBA6H++WXXwIDA4OCgrS0tGAYCwgIUFNTU1dXx+FwrKyskGbm5eU9d+7c5uZmf38/CNkDhZeLi0tZWdnOzu7rr7+GcIkgyOLiIh0dnaWlpZeX1/Xr19PT00VERCBqIwji5+f35MkTHx8fBQUFExMT0K9//vx5S0vLsWPH/P39FRUVxcXFw8LCSkpKjIyMoLGzuroaRLzRIJKQkHD+/HmgIAsICCwtLVFSUpqbm6uqqoLXR0FBwZe8+F8UNezt7WEaBvY/Hh4ezMzMfn5+hw4devDgQWtrKy8v79mzZyETw8DAYGlpWVBQoKCgkJ6eTkFBkZycHBERISkp6eHhkZ2dbW9vLy8v/+jRo3Pnzs3NzU1PT3/zzTfw3sbFxR05ciQ/P//169dgJgIPh6+v73fffYeKSuzs7GCx2IiICCwWi8ViZWRkHj58mJmZWVdXJyUlxczMnJ+fT0dH5+Pjk5OTk5GRQUZGZmFhERsbOzg4SE5Orq6uHhgYCDuPjIx89erVmTNnlJSUBAQE6Onp0RIMBoM5e/YsFot1dHTc2tra3t4mJSV9R2bi3r17vLy8Tk5OFy5cyMrKysvLO3v2LEy/1dXVMRgMpAy2trZMTExYWVmVlZVPnTq1uLgYGRl59epVRUVFFhYWW1vbzMxMfn5+HR0dIyOjhYUFFxcXcPEQFRU1MzPj4eEJCAhwcXHZv0wtLy+/fv36vXv35ufnm5ub6ejonjx5MjMzIyoqGhUVBer7ysrKkFpDEKSqqoqTk1NaWvr48eN1dXX9/f0CAgIyMjKysrJPnjzp6+tTVlZ++PChra3t1tZWVFQUHx9fUFCQhITE48eP1dTU0D6onp6ee/fuubi4VFZWysjIyMnJFRQUVFdXi4uLq6urQ5jQ0NCYmZmBXkQZGRkNDY2pqSl9fX0VFRVZWVl5efmuri4bGxs5OTkwlyAQCDY2NtLS0o6Ojnp6etPT035+fuLi4o8fP94vLOLt7Q0DUkBAACzZoqOjZWRkfH19vby8EhMTFRUVnZyc9ru3ubm5PXjwwMPDo6amxtzcPCoqKigoCIvF1tTUFBcXu7q65uXlkZCQqKqqxsTEbGxsdHR0GBoaJiYmzs/POzs76+vro5UpFxcXNChUVVVhsdgnT54MDw8PDAxYW1uHh4eHhISAARh8Jjk52cPDY2trKy0tzdLSEvU0QBCktrbWxMQkODh4YmKCQCDExsY+fvy4pqamq6srOjq6vb19aWkpISEhJiZmcHBwc3MzLS0tNja2v79/ZWUlNTUVdHkRBMHj8enp6Y2Njbm5uampqYuLi5OTkzMzM6DqnJWV9fbt2z83Gwpl9g8eQ15e/vjx4+7u7lCJnJ+ft7a29vb2zs3NjYqKysvLs7a2hhYGBEHo6elv3rzp4uICU9bc3FwNDQ03N7eJiYnCwkJVVVWwtImJiTEzM4NNEhMTwdhqb28vPT0di8UGBga+efPG3Nw8MjISQZCKigqYiaHIz883NTWNiYkBk8HQ0FAPD4/29vbs7OzExMSVlZW2trbw8PDs7Ozd3d03b95ERERkZmbu7u6Wl5dnZWXt7OyUlZVFRESAOAVIMPT399fU1OzPsGZnZ6Optb29PWhg338aU1NTTU1Nb968qayshJ6ouro6cCEuKioCkjWKxsbGoqKi06dPQ+K2paVlYGBgbW0Njgi2b/DJra2t1tbW3d3dlZUVyNXPz8/Pz8/vb5xbWloC7eXt7e3V1dWpqSl4RNDk9Orq6jsCXKDDTE9PD9mWzc3Nd8pJn9G28IV8Zy0tLXS1/9lAU+yfgZycnAMHDtTV1X3kM3g8vq6uTkZG5hMr8f9n8NtRY2lp6Z0OGcDe3h4vL6+YmNhv7gHcqC5evAiFKxT7p/Tv8H92d3d/08C5s7NTVVU1OTn5N0/gz8ObN2/U1NTMzMy+cD8JCQlERESoO/mXYHt7+9fIVB9BZWXlwYMHYeX1twCkiZD/dbe/desW6kLy2djZ2fns4AW2Zh8vWnd0dLCyskKG6P9X+O2oAdaq7/8d7OdkZWU/5dYWFRWBgc3nnOOHsLOzY2xsbGxs/Df28CAI8vr1ax0dnd/0tf9NVFRUBAQE/CF0rOXl5Q+KBn4cg4ODtbW1/xA5742NjcHBwZGRkf1zqL8Y0Dz2vgv3O/jggPp/Hl/UKQ8//CZfdX+H2B9FUPuSrrM/8DT+yfi1deWXYHd3d2lpCV5mAoGwtLT0KT4pX3Ias7Oz79DkgAq0f59LS0uopRB6xJGREWgI/hTq0J8BPB6flZVVVlYGC6U/e3gjEAhxcXE+Pj4EAmFwcPAdcbw/Fn8PN3RhYaGlpeWvNx/a3t7u7e1FaWl/HgYGBnJycj6yUoDSI+pm9uXIzMw0NTV1cHAwMzOzt7cHehLqcflHYX19XUJCAtxMJycnSUlJXVxcEARZW1v7+LIoPj7ewsLi9172ra0tVVVVGhoaVOlnYGBAW1v7ncldWlramTNn9tcFtra2uLm5wU4ROFdzc3Pv5J7+bMzNzV27du3hw4ebm5v8/PwgL/Bn2MqgMDAwOHv27OLioru7O8i1/kn4e6LGy5cviYmJUWW0Pxt4PP7FixcbGxtv3rxRUFD48/y+Zmdnvb29V1dXy8vL5eXlPzIOV1dXf//995DT/SB+7wvm5eXl7+9vbGzMxMSUnZ2NwWAYGBigLr4f8G7/2s7RCTmMz9vb28D3hQ2hWuzj40NLSwufuX37toWFxfr6OirMMT09DW/45ubmzs7O5uYmHo/f3t7G4XCJiYkg47y2trZ/Yj8yMvJOdnZ8fBwdmRMTE69duzY5OQl5zdnZ2aysLEjWoiTgxcXFq1evtra2Tk9Poxvq6OiIiYmtrq6mp6fPzc1ZW1srKyvDSY6OjsKGy8vLi4uLsOf5+fnOzk6YlSwsLCwvLw8MDAwPD4+Pjy8tLU1PT4OVL4Igu7u7DQ0N/f39oK8xPj6+vr4+PT0NX2p+fr6pqQnqhoaGhtra2vPz83AO3t7eHBwcYAM+PDy8urra3t4OKfCNjY2amhrUzAE2gUFleno6NjYWVq9DQ0PR0dE4HA5y+fX19dnZ2WNjY5ubm0VFRdbW1pycnDMzMzk5OWAQWVVVlZKSAlLMCIJUV1eHhISUlZWh3/Tz8PlRA7rIRkdH6+rq0PcQSCkIguDx+MHBQfD42NraQseK0dFReBDJycmh5gQPHDqdHh0dhbsIf2lpaYGBZXFxcW5ubmBgYH5+nkAggEM3giCzs7NVVVUwF52bm8PhcLD56OjowMBAXV3dzs4OUHE6OjoGBweLioqWl5fb29t7enoSEhJg/Nna2kpJSQGaBnyXtra2kJAQVJZqdHQ0JycnLy8vKCiotbV1b2+vpqbmyZMn1dXVa2trSUlJOTk5vr6+sbGxJ0+ezM7Ozs/Ph0Rab2+vhYWFr69vbW1teHh4X19fSkpKfHz82trazZs3ExMTJycn3d3d7e3te3t7W1tbnzx54uDg4O7uDrc5IiICg8G8ePGitLTU3t7ewMAgPj6+sLBQT0/P2tp6f/4CvnVISAhaVFJSUuLk5NTQ0LC2tl5bW5ucnHR0dDQwMABZoKKiIm1tbV1dXTk5OaAtBQUFGRkZmZiYtLW1PX78WENDY2JiwtTU1NPTs6WlxcbGRk1Nrby8PCMjA7g2CILo6urS0dEpKiqCrHFCQoK0tPT9+/e7urr8/PwUFRX7+vqMjIzs7e3NzMzc3NyqqqoEBASkpaXZ2Nh8fHyWl5c9PT319fWh9Nvd3b2zs+Pk5CQmJiYrKwtBKisr68yZM1JSUqBQC+7wKysrBQUFFhYWysrK9+/fd3d3v3Hjhpqa2u3btzEYDARrFxcXGxuburo6QUHB6upqPj4+EhKS3NzcsLAwBwcHRUXF2NhYa2vr69evs7GxhYSEeHl58fHxmZqaLi8vKygoMDExXbhw4ebNm3fv3h0fH3/w4AHQqEZHR7FYrKmpKRsbm42NTUhICB0d3fDwsJaWlpyc3MzMDBaLFRYWFhMT297eNjExMTQ0zMvLu3TpUlFRkbKy8okTJ6ytramoqIyNjbu6ui5cuFBfX7+7u+vl5QWCz5GRkYODg8rKyvr6+jIyMqmpqQoKCpaWluLi4qmpqVJSUm5ubiwsLL6+viYmJufPn2dhYQkKCnr06JG3t7eIiIiIiMj09DQlJWVAQICHh8ehQ4e0tLRoaGhCQkLy8/PFxcVDQ0P/85//oFfp8/D5UaOvr4+enp6KiurevXuCgoLz8/Ourq4YDEZERERFRWVsbIyPjw9Ynp6enoKCgr29vXZ2drq6uhoaGpOTk5ycnFDW8vPzo6KiYmVlDQ8PT0hIsLW1lZWVDQkJkZeX5+LiUlJSoqCgeP78+aNHjy5cuHDr1i0XFxdra2sLCwsBAYGwsDCQDsVisTk5Ofr6+ra2tmJiYoGBgaSkpPDaWFpaJiYmHjlyRF9f39raWkREpKenh4yM7O7du/Asjo2NGRgYODo6ioqKkpCQAJHBwcHBysrqzJkzILGXn59//PhxFRUVDAZDQ0MDpWUMBnP9+vXm5mYuLq7z58+LiorKycn99NNPT58+NTQ0vHXrVmVlpaqqqru7u7S0tJ2d3ZkzZ0DxHFjSQkJChYWFZWVl4LeOwWCKi4v//e9/c3Bw6OrqwpPExMQUERFx5swZT0/PAwcOsLCw+Pj4REREeHt7Hz9+/P1ZqK+vL9rFJCMjw8XFVVpaeu7cuefPn8vLywPJ4sSJE5OTk+3t7V9//XVERISBgYGAgICfn9/t27e7uroUFBRERES8vb1PnTo1OTkpKiqamJh469YtDAajpKTEzc39/PnzBw8ewCGAdtHS0kJOTp6fn5+Tk+Pj43PkyBE3N7fy8vJTp041NjbKysqWlJSYmpqKiorOzs6eOHEiMjIyLCzs6tWrHh4eV65cgaKvhobG0tLSzs5OWlqak5PTv//9b1hxpKamUlJS9vb2Ghsb37lzp6CggJGRcWBg4MaNG2AdQEdH19raSkVFFRYW1tTUREpKCm0+Hh4elpaW0HUGcRZc74mJiYOCgvj5+YWEhOzs7Ojp6SsqKioqKlJTU+Xl5YE1o6enx8TE1NXVlZCQwMDA0NHRoaqqChMBa2trGRkZBEHMzc0xGExubu61a9cQBAkPD2djY9vc3IyMjLS0tIQ6uoWFhb6+/sbGBhkZWXl5ua2t7Z07d7a3t11cXBQVFcvLy1FneRwOFxcXR0tLy8fHZ2FhAY2qQ0ND165dc3V1RRBkfHycl5dXQkICQRBvb++bN2/Gxsby8/MvLy8/efIEbnplZeWdO3d2d3ehk6WpqQmUX21sbLS0tNzd3UVFRcvKym7duvWF0+0vWqGIiIjIycnh8XhycvK4uLgbN25sbW11dXV99913SUlJOBzum2++aW9v9/DwCAwMNDc3p6Oje/HixbVr1yIiIu7du9fW1oYgSHt7+7Fjx+Lj458/f37u3DnQENTR0VFWVhYUFEQQxMHBgY+PLyUl5fz582/evHFxcbl8+XJQUBATE5O4uDgbG5uenl5mZqawsDAnJydoozs7O5OSkr5+/To/P5+UlPTVq1fMzMxv374dGhri4OAYGxsD64qdnZ3r16/HxMRcuXKltrZWV1cXKK3b29vx8fFmZmbfffcdjMwLCwvs7OwgFHjz5s3g4ODIyEgtLa3jx4+3trZ6eHjAi1RWVgZC1a9fv+bi4sJgMFCUXV9fb25upqKi2tnZgTaQ7e1tFhaWxMTEoqIiQ0NDLi4uMTGxyclJLi4ulKsjLi5OSkoaGxvr6OjY2NjIzMwMvABbW1s7OzvQ74RPoiuOoKAglAEpJSVlbGyMIAgXF5euru6VK1eUlZVDQ0MjIiJg1UBLSws+bPfv33/w4AF8heDgYAoKiuHhYRYWFnV1dWdn58nJSWJiYgwGk5CQ0NDQkJyczM/PD4dQVFR0dnZGEISNjc3Ozs7Z2fnZs2dsbGzA1oVeDLCG8vf3v3//PoIgdHR04+Pj1dXVV65cycrKunnzpp6enp6e3vDwMNi7Kyoqenl5nT59Gmrqqamp8OiHhITcv3+/u7ubh4dncXHRzMxMQkLC1dUVyC9Xr15tb2/f29s7fPgw3KaAgADoV2RlZa2srDQ1NQXV0kOHDvn7+xcUFIyOjkJXG4IgcXFxUlJSWCyWmJgYQRA7Ozs4WwRBJCQk2NnZUR6dkpKSuro6giA2NjbGxsYFBQX09PQIgtjb24uKilZVVXFwcAQHB3///feDg4N2dnbQ73P16tXGxkZPT09hYWEEQYaGhsjIyPj4+GCqOzk5SUlJ6ezsfOfOHU5OTmVlZaDVIwgC0qdwf0HfH0EQNzc3UVHRmJgYAQEBBEEiIiKuXbs2PT0NxgVw6728vMrLy0GKGYvFqqqqDg0N0dDQ6Orqfnlm4IuixoMHD0xNTTc3N+np6aOiosjJyVdXV+fn50+dOgUditAKpaysvLS09ODBAyoqqvT09JqamomJCUZGRsgMzczMXL16FeTnf/zxx4iIiKampunpaRBiRf73cSksLIQr4u7ufuHChcLCwvr6+p6envj4eA0NDTo6unPnzvHz87e2ti4vL/f09Fy4cOHVq1ctLS03btyorKxkYWGZm5tra2ujoKBob2/n4eExNzff2tq6evVqYWHh48ePOTg40B7wV69eXb58OSkp6ezZs+A3s7CwwMbG9vr16+HhYUFBQRMTk5s3b8bFxR08eBCHw2EwGFlZWQRBcDjc2bNn+/r6MjMzb9686ezsTEJC0tvbu7a21tbWduLEiYqKChERkfv3729vb1NQUPj4+DAxMamoqCgqKlJRUTU3N1NTU6O98IaGhqSkpFVVVT09PQ0NDT/88ANodv74449eXl6XL182MDCor6/PyspCfZswGAwZGRmsXDg5OYWFhQkEAszeRUVFJSUli4uLX758SSAQ3rx5c/To0aampvj4eA4OjqCgoEuXLtXW1qqoqIBIurOzMxEREbyBzMzMkpKSGRkZtbW1NjY2586dg+oJBweHkpLS+vo6DQ2NrKwsNTW1ra3tuXPnwJ0gKSmJiIgIWJs6OjqUlJQ5OTmHDx9OSUkpKSn5+eefX79+LSAgwMbGZmFhUVZWtrOzA/LL9vb2P/30k62tLYIgrq6ux44d6+npsba2pqam9vHxOXPmTFtbm5eXFzU1tZ2dXUpKSllZ2ZEjR6ytraempoiIiEDMQl1dnZaWtrq6GnqXHj9+fPHixcjISFCKDQsLq66ulpWVpaCgGB8fNzIyAjOXn3/+OSoqioWF5fLly8AGjouL+/bbb1HbiqSkpDNnzpibm1NTUxsbGw8PD1NSUoqJiV2/fp2Ojs7b25uYmPjRo0c//fSTlZUVKysrMzNzeno6ERGRu7t7bm7ujz/+CN2bIiIiKNepr6/vwIEDd+7cERUVBfF6CgoKUVFRf39/oIrfuXPH19e3srKSnZ1dX19fS0sLSv4MDAzt7e2Li4vc3Nz8/Px8fHzXr1/PyckRFBSUlpY2Nja+cuXK6Oiov7+/jIxMVVXVxYsXJSUlxcTEvjBX+vlRY2ZmhoKCQlFRcXZ2lpqa2sPDQ1NTU1VV1cbGRldXF4pzVVVVX331la+vL4Ig0dHRV65csbOzi4mJqa2tPXLkCESW1NTUb7/9tqysbG5ujoWFRUlJycfHp7W1FXrVnj59qqWlVVlZ6e/vf/r06e7u7u7ubioqKmDyBwUFmZiYBAYGqqioxMbG3rx5E4PBODs7JyUl/fzzz3FxcTgc7tKlS+D3IyEhERAQAN0ErKysKioqHR0ddHR0UVFR5ubmlJSUwEAHHV1aWlpZWVlaWlpwMFhbW2NhYWFmZpaXl8fhcGB+oaamxsrKam5uLiYmJi4uPjU1tbCwwMXFpaqqamFhwcnJWVBQICUlxcnJaW1tPTs7q6urC94Ld+/e9fPzY2JicnBw8PT0FBAQsLKyunPnDkokh5Te7Oysurq6iIhIcHBwYmIiExNTcHDwzMyMgoKCkpKSkZGRn59fQEAAkOsRBJmamjI0NJSTkwPdYH19fSMjo/HxcX9/fxsbm8bGRhMTE21t7ZiYmO3t7RcvXkhISFRWVnZ0dJiamg4NDUEzSHR0NNS2xsfHAwMDISE1MjJiZmamqalZVlaWnp7u7u4+Nja2srISHBwcFRW1sLDw/PnznJyctLS0gICAlJSU8PDwjY0NPB7//Pnz7e3t7e3txMREHx+fmJgYDw+PvLy8ycnJkJCQwMBABgYGV1dXOTm5H3/8EcRlQ0NDg4ODk5KSIDGUmZnp6upaV1fX09Pj5+cXGhr67NkzHA4H/HR3d/cDBw6oqqoGBgY+f/58eXk5MTHx1atXOzs7CQkJeXl5VVVVYL4xNzcXFhbW09OztLTk7e3t5+c3ODiYkpISHBw8ODgIXPX8/HyQYi4pKSkrK4NUUXFx8Ts+AJWVlVFRUbKystD92NTUlJiY2NzcXFlZCWm+6urqrq6ukpKSkpKS2trapqamioqK2tra3d3dmpoaaCZ49OgRalWDIEh/f39paenExMTAwACBQBgfH8/Pz+/u7oYbgf48MjKSm5s7NTW1u7vb09PT1dUFfWigxPH27duBgYG+vj6QWW5ra+vt7cXj8Wtra8PDw7q6utra2uPj4zo6Ol9o+/j5UWN+fj45ObmwsHBpaam8vLy6unpzczMpKekdK+D9jUbgN5WXl9fa2hoYGFhYWAgiTnFxcXl5eQiCDA0NOTo6hoWFLS8v29nZsbOzR0ZGQrr75cuXSUlJ0HLS3d0dFxf36tWr2dnZFy9eJCcnw+ja2dmZkJDQ0dHR39+fmpoKbhGlpaXLy8sdHR2lpaWTk5Pd3d1v3rzp6urq7e1dX18fGxt7/fo1KytrWVlZY2MjERERiBRMTk6OjIzMz89D88Lo6CglJWVYWBia/J+dnYXsN1o+AN4KHo+fm5vbn6AeHBxECdpoCQNyUe8oNsMfURVl+COaSEbeY9CieEeTeT+z9oNsml9ju/yuws1+bZSP7+rXdmtkZERPTz8/P5+bm3v27Fm0T+Q3N5ycnDx16lR5efnIyAgtLe3+1++dcwP8mt7Sx7G7u5uQkMDNzf3+/hEEuXXrFjs7+2doCG9sbFhbW8vLy+Px+OXlZRhfIQp/xkl+OsAjNiwsTF5eHu2X+zx8ZtTY2Nj4s6Wfubi4oEv6z0ZnZyc5OXloaKi7uzsfH98HnaizsrKIiIg+xZj2v/h0DAwMKCkpSUlJaWhofFAo5Newu7vr7+8vLS2toKCQmpr6m8EOysDor6B/9ZtHWV9fx2AwH6SZDA0NOTk5OTg4fEbL+eTkpIaGBlRVobaNIMjS0tLnhbZPx+rqak5OTnJy8pd3zXxm1Njc3PxThZK3trYCAgKcnJz+VIobiqqqKmtray8vrw9yw/f29rq7uzMyMiorK/9iUulnHO73bvK302T/erLfJ+LXrswnXrEvN774k24NsBz/NgXAL8T29vavhZ6//VH+owCLkd9b6Nre3u7p6RkZGfm8qNHQ0FBbW/vOtnNzc/X19e3t7V1dXa2tre3t7S9fvuzq6vqUQ1RWVqanp//Zg+GnYGVlJTo6+tWrVw0NDSEhIZ83dNXW1jo7O79PzK2vrzc3N0fNnD8PCwsLFhYWX2ikWl9fr6Sk1NHRMTw87OTk9Ad2u8TGxtLS0n6K8vZH8Af0oXw2dnZ2PmWi+E/G2tqajY0NEAQ+iOXlZUlJSaiwfDrm5ua4uLigtv/BD4Dq+q9dPUVFRS4urncyCzIyMlJSUrdv36ajo9PU1OTn5ycnJ4ey6G/Cy8uLiIgI9A1RzM7OfqG4y2dga2vr9u3bmpqaycnJJ0+e/MiVLysr+7X3v6Oj47vvvvP09ET/kpmZ+fr166GhoR9++OELNTX39vbAEvBLdrK+vg4y0YODg/Ly8u/Yvn3woJ+45+rq6hMnToDI2Gfji+YaCQkJqMwEij+wUW16etrNze0zOjj/JOxP5aysrBAIhPX1dRD1QWnXoJCMIMj6+jpoGoOjL+gng6r1+vr6/mX29PQ0avI8NTUFRzEyMrpx4wZ8bHh4GM2Jjo2NLS0tzc7OUlFRAQ13bW1taGgItZIbHBz08/NjYWF5J2okJCQsLy+DPfLc3FxJSYmWlpaFhUVrayv6ULa2tr6j/YEgyJs3b/z8/A4cODA